Internal addition type polyolefin seven-layer co-extrusion light-conversion dustproof high-heat-preservation pesticide-resistant long-acting dripping fog-dispersal greenhouse film and preparation method thereof

Through the layered design of polyolefin greenhouse film with a seven-layer coextruded structure, combined with functional materials such as dust prevention, light conversion, insulation and droplet storage, the existing greenhouse film has solved the problem of short effective period of fog removal and difficulty in function coordination, and achieved the effect of long-term fog removal and multi-functional synergy.

CN119526860AActive Publication Date: 2025-02-28SHANDONG AGRICULTURAL UNIVERSITY

Patent Information

Application Number
CN202411725541.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing internally added droplet fog removal shed film has a short effective period, which cannot meet the needs of modern high-efficiency agricultural facilities. It is also difficult to achieve the coordinated coexistence of comprehensive functions such as dust prevention, light conversion, high temperature insulation and anti-pesticides.

Method used

The polyolefin shed film with a seven-layer coextruded structure is adopted. Through the layered design of the outer layer, the outer layer, the outer layer, the inner layer, the inner layer, the inner layer, the inner layer, the inner layer, the inner layer, the inner layer, the inner layer, the inner layer, the inner layer, the inner layer, the inner layer, the inner layer, the inner layer, the inner layer, the inner layer, the liquid dust-proof, the insulation, the drop agent reserve and the sustained release layer are added respectively to achieve the comprehensive functions of long-term drop fog removal, dust-proof, the outer layer, the liquid-controlled, the high insulation and the anti-pestic.

Benefits of technology

The effectiveness period of the drip fog removal function has been extended to more than 24 months, and it also has the functions of self-cleaning, dustproof, dimming and light conversion, high insulation and anti-pestics, meeting the multifunctional needs of modern agricultural facilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005159116520000111
    Figure BDA0005159116520000111
  • Figure BDA0005159116520000121
    Figure BDA0005159116520000121
  • Figure BDA0005159116520000271
    Figure BDA0005159116520000271
Patent Text Reader

Abstract

The invention belongs to the technical field of agricultural film preparation, and particularly relates to an internal addition type polyolefin seven-layer co-extrusion light-conversion dustproof high-heat-preservation pesticide-resistant long-acting dripping fog dispersal greenhouse film and a preparation method thereof. The greenhouse film is composed of a first outer layer which is a dustproof anti-aging layer, a second outer layer which is a light conversion anti-aging layer, a third outer layer which is a barrier heat preservation anti-acid anti-aging layer, a middle layer which is a high heat preservation anti-acid dripping agent storage layer, a third inner layer which is a high heat preservation anti-acid dripping agent storage layer, a second inner layer which is a high heat preservation anti-acid dripping antifogging agent slow release layer and a first inner layer which is an anti-acid dripping antifogging agent release layer. The width of the greenhouse film is 8 m or above, and the thickness of the greenhouse film is 0.08 mm-0. 15 mm; the light transmittance is more than 90%, and the haze is less than 16%; the infrared transmittance is less than 20%; 600 days after film covering, the light intensity ratio inside and outside the greenhouse is still larger than 88%; due to the dustproof function, the annual attenuation rate of the light transmittance is smaller than 1.1%; the lasting period of the dripping fog dispersal function lasts for 24 months and is synchronous with the service life of the film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of agricultural film preparation, and specifically relates to an internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-heat-insulating, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film and a preparation method thereof. Background Art

[0002] Agriculture is the foundation of the national economy, and greenhouse films are important materials for agricultural facilities and horticulture. At present, my country's polyolefin agricultural greenhouse film production and annual consumption of about 1.05 million tons are among the highest in the world, and the market development speed of multifunctional high-end agricultural greenhouse films is growing at a double-digit rate every year. There are two main types of functional greenhouse films for greenhouse covering materials on the market.

[0003] The first is the coating type greenhouse film: it can achieve the function of dripping and defogging in full synchronization with the service life of the film. However, due to the long process, high equipment cost, relatively complex process, and high requirements for the performance and quality of the coating liquid, it is more suitable for the production of high-end greenhouse films with a service life of more than 3 years; the second is the internal addition type dripping and defogging greenhouse film: it is produced using the traditional masterbatch processing technology, and dust-proof masterbatch, light-converting masterbatch and various surfactant dripping and defogging masterbatch are added to the film to prepare light-converting dust-proof dripping and defogging greenhouse film. The function of dripping and defogging is achieved through the gradual precipitation of surfactants in the film. The internal addition type dripping and defogging greenhouse film is simple to operate, has low processing energy consumption, and good quality stability, but the dripping and defogging lasts only 4-7 months, which cannot meet the needs of the development of modern efficient agricultural facilities. If the effective period of dripping and defogging is increased to more than 24 months, and the functions of light conversion, dust prevention, high heat preservation and pesticide resistance are added at the same time, the market development potential is huge. However, the mechanism of action of the internally added dripping and mist elimination greenhouse film is to achieve migration and precipitation through the concentration gradient of the dripping agent in the film, produce a dripping effect and flow along the film surface, which is completely different from the coated greenhouse film that relies on the absorption of water vapor in the greenhouse to fill the porous gaps of the inorganic adhesive. When the concentration gradient of the dripping agent tends to zero, the dripping performance is completely ineffective. To achieve a stable and long-term dripping and mist elimination function, it is necessary to solve the problem of sufficient storage and uniform precipitation of dripping agents and mist elimination agents. At present, the comprehensive functional synergy of long-term dripping, dust prevention, light conversion, high thermal insulation and pesticide resistance in the internally added greenhouse film is still relatively backward. Restricted by the relative synergistic effect or negative synergistic effect of processing equipment performance and functional additives, the dust prevention, light conversion, high thermal insulation, pesticide resistance and dripping and mist elimination functions on the market cannot coexist synergistically, and only two or three functions are available.

[0004] Due to the high multiple cropping index of plastic greenhouses, the use of fertilizers and pesticides has increased too quickly. The sulfur and chlorine components contained in pesticides will form sulfurous acid (H2SO3) and hydrochloric acid (HCl) with water molecules in the greenhouse during use, and react with the strong alkaline hindered amine light stabilizers 944 (NH type is alkaline) and 783 to react with acid-base neutralization, thereby passivating the activity of the hindered amine light stabilizer in the agricultural film, making it unable to capture the oxidative free radicals that cause the polymer chain to break, and accelerating the disintegration and damage of the greenhouse film. Sulfur- and chlorine-containing pesticides have a great impact on the weather resistance and life of greenhouse films. In order to solve the problems existing in the prior art, it is urgent to develop multifunctional greenhouse films with comprehensive functions and more reliable quality. The invention of an internally added high-end comprehensive functional greenhouse film meets market demand and achieves long-term dripping and mist elimination for more than 24 months, while achieving self-cleaning and dustproofing, light conversion, high heat preservation, and pesticide resistance functions, which is the subject of the present invention. Summary of the invention

[0005] The purpose of the present invention is to provide an internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high heat preservation, pesticide-resistant, long-term dripping and fog-eliminating greenhouse film. The greenhouse film has the comprehensive functions of dust prevention, light adjustment and light conversion, high heat preservation, pesticide resistance, and long-term dripping and fog-eliminating period; the present invention also provides a preparation method thereof.

[0006] The internally added polyolefin seven-layer co-extruded light-converting dust-proof high-insulation pesticide-resistant long-acting dripping and fog-eliminating shed film of the present invention is composed of an outer 1 layer, an outer 2 layers, an outer 3 layers, a middle layer, an inner 3 layers, an inner 2 layers and an inner 1 layer; wherein the outer 1 layer is a dust-proof and aging-resistant layer, and the outer 1 layer is composed of the following raw materials by mass percentage: 80%-88% of metallocene linear low-density polyethylene (mLLDPE), 5%-10% of acid-resistant and aging-resistant masterbatch, and 7%-10% of dust-proof masterbatch; the outer 2 layers are light-converting and aging-resistant layers, and the outer 2 layers are composed of the following raw materials by mass percentage: 20% of low-density polyethylene (LDPE); %-30%, linear low-density polyethylene (LLDPE) 15%-25%, metallocene linear low-density polyethylene (mLLDPE) 35%-45%, light conversion masterbatch 8%-12%, acid-resistant and aging-resistant masterbatch 5%-10%; the outer three layers are barrier, heat-insulating, acid-resistant and aging-resistant layers. In terms of mass percentage, the outer three layers are composed of the following raw materials: low-density polyethylene (LDPE) 15%-25%, metallocene linear low-density polyethylene (mLLDPE) 55%-65%, acid-resistant and aging-resistant masterbatch 5%-10%, insulation masterbatch 10%-15%; the middle layer is high insulation The anti-acid dripping agent reserve layer is composed of the following raw materials in the middle layer by mass percentage: 57%-68% ethylene-vinyl acetate copolymer resin (EVA), 5%-10% anti-acid and aging resistant masterbatch, 15%-25% dripping masterbatch, and 8%-12% thermal insulation masterbatch; the inner three layers are high thermal insulation anti-acid dripping agent reserve layers, and the inner three layers are composed of the following raw materials by mass percentage: 60%-72% ethylene-vinyl acetate copolymer resin (EVA), 5%-10% anti-acid and aging resistant masterbatch, 15%-18% dripping masterbatch, and 8%-12% thermal insulation masterbatch; the inner two layers are high thermal insulation anti- The acid drip and defogging agent sustained-release layer, calculated by mass percentage, the inner two layers are composed of the following raw materials: 67%-72% of ethylene-vinyl acetate copolymer resin (EVA), 5%-10% of acid and aging resistant masterbatch, 12%-15% of drip masterbatch, 1%-3% of defogging masterbatch, and 5%-8% of thermal insulation masterbatch; the inner 1 layer is the acid drip and defogging agent release layer, calculated by mass percentage, the inner 1 layer is composed of the following raw materials: 77%-84% of ethylene-vinyl acetate copolymer resin (EVA), 5%-10% of acid and aging resistant masterbatch, 8%-12% of drip masterbatch, and 1%-3% of defogging masterbatch.

[0007] in:

[0008] The specific parameters of the raw materials used in the outer 3 layers, outer 2 layers, and outer 1 layer are as follows:

[0009] The density of low-density polyethylene (LDPE) is 0.920-0.923 g / cm 3 , the melt index (MI) is 0.2-0.75g / 10min; preferably, the low-density polyethylene (LDPE) is any one or both of 2420D or 2426F produced by Daqing Petrochemical.

[0010] The density of linear low-density polyethylene (LLDPE) is 0.918-0.922 g / cm 3 , the melt index (MI) is 0.8-1.0g / 10min; preferably, the linear low density polyethylene (LLDPE) is any one of 1001AV produced by ExxonMobil, 9085 produced by Tianjin Union Carbon or 0209AA produced by Shanghai Secco.

[0011] The density of metallocene linear low-density polyethylene (m-LLDPE) is 0.918-0.927 g / cm 3 , the melt index (MI) is 0.5-1.0g / 10min; preferably, the metallocene linear low-density polyethylene is any one or more of 2010MA, 1018MA, 2005MC or 2705MC grades produced by ExxonMobil.

[0012] The dust-proof masterbatch is brand EFT997 produced by Tianjin Riken Co., Ltd.; or brand BE-10F maleic anhydride grafted dust-proof masterbatch, produced by Jilin Baien Plastic Technology Co., Ltd.

[0013] The raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in each layer are as follows:

[0014] Calculated by mass percentage, the acid-resistant and aging-resistant masterbatch is composed of the following raw materials: 45%-53% of low-density polyethylene (LDPE), 30%-40% of linear low-density polyethylene (LLDPE), 12%-15% of light stabilizer, and 2%-3% of antioxidant.

[0015] Wherein: the melt index (MI) of the low-density polyethylene (LDPE) in the acid-resistant and aging-resistant masterbatch is 2.0g / 10min, preferably any one of the 2102TN00 produced by Qilu Petrochemical or the 2426H produced by Daqing Petrochemical; the melt index (MI) of the linear low-density polyethylene (LLDPE) is 2.0g / 10min, and the appearance is powder. Preferably, the linear low-density polyethylene (LLDPE) is 7042 produced by Qilu Petrochemical or 1820 produced by Tianlian Chemical. The light stabilizer is any one of the following: the light stabilizer is a hindered amine acid-resistant light stabilizer, and the hindered amine acid-resistant light stabilizer is at least one of 2011AR, XT-100 or T-69. The manufacturers of 2011AR and XT-100 are BASF, and the manufacturer of T-69 is Beijing Tiangang Company. The antioxidant is a composite type of hindered phenols and phosphites, and preferably, the antioxidant is any one of B215 or B225. The manufacturers of B215 or B225 are both Tianjin Lianlong Company.

[0016] The preparation method of the acid-resistant and aging-resistant masterbatch is as follows: low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), light stabilizer and antioxidant are added into an internal mixer in proportion for kneading and plasticization, and then fed into a single-screw extruder granulator through an open mixer, and then hot pelletized and air-cooled and dried to obtain the acid-resistant and aging-resistant masterbatch.

[0017] Wherein: the temperature of the internal mixer is 125-140°C, the plasticizing time is 15-20 minutes, and the temperature of the single-screw extruder granulator is 140-170°C.

[0018] The thermal insulation masterbatch is composed of the following raw materials in mass percentage: 18%-25% low-density polyethylene (LDPE), 15%-20% linear low-density polyethylene (LLDPE), 55%-65% hydrotalcite thermal insulation agent, 1.0%-2.0% coupling agent, 0.5%-1.5% lubricant, and 0.5%-1.5% dispersant.

[0019] Wherein: the melt index (MI) of the low-density polyethylene (LDPE) in the thermal insulation masterbatch is 2.0g / 10min, preferably any one of the 2102TN00 produced by Qilu Petrochemical or the 2426H produced by Daqing Petrochemical; the melt index (MI) of the linear low-density polyethylene (LLDPE) is 2.0g / 10min, and the appearance is powder, preferably, the linear low-density polyethylene (LLDPE) is any one of the 7042 produced by Qilu Petrochemical or the 1820 produced by Tianlian Chemical; the hydrotalcite thermal insulation agent, preferably the brand is HTP, manufactured by Sakai Chemical Co., Ltd. of Japan, or any one of the brand HT3 produced by Dandong Kyowa Company; the coupling agent is any one of titanate or aluminate, both of which are produced by Qingdao Jisi Chemical Co., Ltd.; the lubricant is two or any one of zinc stearate or calcium stearate produced by Hebei Zhongshang Chemical; the dispersant is polyethylene wax.

[0020] The preparation method of the thermal insulation masterbatch is as follows: low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), hydrotalcite thermal insulation agent, coupling agent, lubricant and dispersant are added into an internal mixer in proportion for kneading and plasticization, and then fed into a single-screw extruder granulator through an open mixer, and then hot pelletized and air-cooled and dried to obtain the thermal insulation masterbatch.

[0021] Wherein: the temperature of the internal mixer is 125-140°C, the plasticizing time is 15-20 minutes, and the temperature of the single-screw extruder granulator is 140-170°C.

[0022] Calculated by mass percentage, the light conversion masterbatch is composed of the following raw materials: 36.6%-49.8% low-density polyethylene (LDPE), 38%-45% linear low-density polyethylene (LLDPE), 12%-18% light conversion agent, and 0.2%-0.4% antioxidant.

[0023] The low-density polyethylene (LDPE) in the light-converting masterbatch has a melt index (MI) of 2.0 g / 10 min, preferably any one of the grades 2102TN00 produced by Qilu Petrochemical or 2426H produced by Daqing Petrochemical; the linear low-density polyethylene (LLDPE) has a melt index (MI) of 2.0 g / 10 min, and the appearance is powder, preferably, the linear low-density polyethylene (LLDPE) is 7042 produced by Qilu Petrochemical or 1820 produced by Tianlian Chemical. any one of; the light conversion agent is preferably an inorganic rare earth light conversion agent, and the inorganic rare earth light conversion agent is any one or more of green to red GTR-650Ⅱ, green to red GTR-650Ⅲ, purple to blue VTB-440 or purple to red VTR660, all of which are manufactured by Hunan Xiweier Technology Co., Ltd.; the antioxidant is a composite of hindered phenols and phosphites, and preferably, the antioxidant is any one of B215 or B225; the manufacturers of B215 or B225 are Tianjin Lianlong Company.

[0024] The principle of selecting the light converter is that the excitation spectrum of the light converter matches the sunlight spectrum on the ground, and the emission spectrum matches the absorption spectrum of chlorophyll. According to the light quality requirements of crops, chlorophyll a mainly absorbs blue-violet light at 418nm and red light at 660nm; chlorophyll b mainly absorbs blue light at 454nm and red light at 643nm; β-carotene mainly absorbs blue-violet light at 400nm-500nm. Select one or more photoconversion agents to convert the ultraviolet light region of 290nm-390nm and green light region of 500nm-580nm, which are difficult for crops to absorb, into the best growth effect spectrum with high crop absorption rate, the blue-violet light region of 400nm-500nm, and the main peak of the emission spectrum of 440nm±30nm; the red light region of 600nm-700nm, and the main peak of the emission spectrum of 650nm±30nm, so that the converted blue-violet light and red light can be radiated into the greenhouse as much as possible, to adjust and improve the lighting environment in the greenhouse, improve the photosynthetic efficiency of crops, and achieve the effect of improving quality and increasing yield.

[0025] The preparation method of the light conversion masterbatch is as follows: low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), a light conversion agent and an antioxidant are added into an internal mixer in proportion for kneading and plasticization, and then fed into a single-screw extruder granulator through an open mixer, and then hot pelletized and air-cooled and dried to prepare the light conversion masterbatch.

[0026] Wherein: the temperature of the internal mixer is 125-140°C, the plasticizing time is 15-20 minutes, and the temperature of the single-screw extruder granulator is 140-170°C.

[0027] The melt index (MI) of the ethylene-vinyl acetate copolymer resin (EVA) in the raw materials of the middle layer, the inner three layers, the inner two layers and the inner one layer is 0.25-1.0g / 10min, wherein the VA content of the ethylene-vinyl acetate copolymer resin (EVA) in the middle layer is 19%, the VA content of the ethylene-vinyl acetate copolymer resin (EVA) in the inner three layers is 14%, the VA content of the ethylene-vinyl acetate copolymer resin (EVA) in the inner two layers is 12%, and the VA content of the ethylene-vinyl acetate copolymer resin (EVA) in the outer one layer is 7.5%.

[0028] Preferably, the brand of ethylene-vinyl acetate copolymer resin (EVA) is any one or more of FL00012, FL00014, 00111, 00119 produced by ExxonMobil, and 2050, 2040, 2030 produced by Hanwha Corporation.

[0029] Measured in percentage by mass, the drip masterbatch in the raw materials of the middle layer, the inner three layers, the inner two layers and the inner one layer is composed of the following raw materials: 37%-42% of ethylene vinyl acetate (EVA) resin, 30.6%-36.4% of linear low-density polyethylene (LLDPE), 18%-22% of drip agent, 0.4%-0.6% of antioxidant and 5%-8% of ultrafine silica.

[0030] Wherein: the melt index (MI) of the ethylene-vinyl acetate (EVA) resin in the drip masterbatch is 2.0 g / 10 min, preferably 14-2 with a VA content of 14% produced by Beijing Yanshan Organic Chemical; the melt index (MI) of the linear low-density polyethylene (LLDPE) is 2.0 g / 10 min, and the appearance is powder, preferably, the linear low-density polyethylene (LLDPE) is any one of 7042 produced by Qilu Petrochemical or 1820 produced by Tianlian Chemical; the drip agent is any one of KF650 or LD777, KF650 is produced by Tianjin Riken Kaisha; LD777 is produced by Qingdao Siwei Chemical, the antioxidant is any one of B215 or B225; the manufacturers of B215 or B225 are both Tianjin Lianlong Company; the ultrafine silica is any one of J430 or J430B produced by Foshan Jinchun.

[0031] The preparation method of the drip masterbatch is as follows: ethylene vinyl acetate (EVA) resin, linear low-density polyethylene (LLDPE), drip agent, antioxidant and ultrafine silica are added into a high-speed mixer according to proportion and kneaded, and then the kneaded material is fed into a twin-screw extruder granulator, and the drip masterbatch is obtained after drawing, water cooling, pelletizing, drying and cooling.

[0032] Wherein: the temperature of the high-speed mixer is 75-85°C, the kneading time is 12-15 minutes, and the temperature of the twin-screw extruder granulator is 150-175°C.

[0033] In terms of mass percentage, the defogging masterbatch in the raw materials of the inner 2 layers and the inner 1 layer is composed of the following raw materials: 45%-52% ethylene-vinyl acetate (EVA) resin, 35.9%-43.7% linear low-density polyethylene (LLDPE), 8%-12% defogging agent, and 0.1%-0.3% antioxidant.

[0034] Wherein: the melt index (MI) of the ethylene-vinyl acetate (EVA) resin in the defogging masterbatch is 2.0 g / 10 min, preferably 14-2 with a VA content of 14% produced by Beijing Yanshan Organic Chemical; the melt index (MI) of the linear low-density polyethylene (LLDPE) is 2.0 g / 10 min, and the appearance is powder, and the preferred linear low-density polyethylene (LLDPE) is any one of the 7042 produced by Qilu Petrochemical or the 1820 produced by Tianlian Chemical; the defogging agent is any one of KF38 or TS403 fluorosurfactants, KF38 is produced by Tianjin Riken Kaisha, and TS403 is produced by Dalian Jinlong Chemical; the antioxidant is any one of B215 or B225; the manufacturers of B215 or B225 are both Tianjin Lianlong Company.

[0035] The preparation method of the defogging masterbatch is as follows: ethylene vinyl acetate (EVA) resin, linear low-density polyethylene (LLDPE), defogging agent and antioxidant are added into a high-speed mixer according to proportion and kneaded, and then the kneaded material is fed into a twin-screw extruder granulator, and then subjected to strip drawing, water cooling, pelletizing, and entering a drying device, and then cooled to obtain the defogging masterbatch.

[0036] Wherein: the temperature of the high-speed mixer is 75-85°C, the kneading time is 12-15 minutes, and the temperature of the twin-screw extruder granulator is 150-175°C.

[0037] The internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high heat-insulating, pesticide-resistant, long-acting dripping and fog-eliminating shed film described in the present invention has a thickness ratio of 1:1:1:1:1:1:1:1 among the inner 1 layer, the inner 2 layers, the inner 3 layers, the middle layer, the outer 3 layers, the outer 2 layers, and the outer 1 layer.

[0038] The internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film described in the present invention is adjusted in formula and added with dust-proof masterbatch and acid-resistant and aging-resistant masterbatch in the outer layer according to the layered additional functions. After the greenhouse is covered, the outer layer facing the outside of the greenhouse can play the role of self-cleaning and dust-proof, resist light-heat oxidation degradation, and improve the aging resistance function; the light-converting masterbatch and acid-resistant and aging-resistant masterbatch are added to the outer two layers. The main function is to select one or more light-converting agents according to the crop's demand for light quality, and convert the ultraviolet light and green light that are difficult for crops to absorb into blue light and red light with high crop absorption rate to meet the optimal growth action spectrum, so as to adjust and improve the lighting environment in the greenhouse, improve the photosynthetic efficiency of crops, reduce some insect pests, and increase the yield, early maturity and good quality of fruits and vegetables; the outer three layers innovate the dripping agent to guide the inner layer precipitation design scheme, that is, the metallocene resin with higher density is added with hydrotalcite insulation masterbatch and acid-resistant and aging-resistant masterbatch, which plays a role in blocking the outward migration of the dripping agent, which is beneficial to prolonging The drip function is long-lasting, and it also has the function of blocking infrared radiation to the outside of the shed at night and on cloudy days; the middle layer is added with ethylene-vinyl acetate (EVA) resin with a VA content of 19%, hydrotalcite thermal insulation masterbatch, acid-resistant and aging-resistant masterbatch, and drip masterbatch as a drip agent reserve function, while thermal insulation, acid-resistant and aging-resistant; the inner 3 layers are added with EVA resin with a VA content of 14%, hydrotalcite thermal insulation masterbatch and acid-resistant and aging-resistant masterbatch, and drip masterbatch is added as a drip agent reserve Function, at the same time, it plays the insulation function of blocking infrared radiation to the outside of the shed, and it is also resistant to acid and aging; EVA resin with VA content of 12% and hydrotalcite insulation masterbatch, drip masterbatch and defogging masterbatch are added to the inner two layers, which have a slow-release function for the drip and defogging agent, and acid and aging resistant masterbatch is added, which is acid and aging resistant; EVA resin with VA content of 7.5% and drip masterbatch and defogging masterbatch are added to the outer layer, which has the function of controlling the release of drip and defogging agent, and acid and aging resistant masterbatch is added to resist acid and aging.

[0039] The preparation method of the internally added polyolefin seven-layer co-extruded light-converting dust-proof, high heat preservation, pesticide resistance and long-acting dripping and fog-eliminating shed film described in the present invention is as follows: the component materials of the outer 1 layer, the outer 2 layers, the outer 3 layers, the middle layer, the inner 3 layers, the inner 2 layers and the inner 1 layer are respectively mixed and stirred evenly, added into a seven-layer co-extruder, and subjected to melt plasticization blow molding, cooling and shaping, pulling, slitting, edge welding, coding and marking, and winding to obtain the internally added polyolefin seven-layer co-extruded light-converting dust-proof, high heat preservation, pesticide resistance and long-acting dripping and fog-eliminating shed film.

[0040] Wherein: in the seven-layer co-extrusion unit, the extruder temperatures of the outer layer 1, outer layer 2, outer layer 3, middle layer, inner layer 3, inner layer 2 and inner layer 1 are all 150-200°C, the die head temperature is 190-210°C, and the blow-up ratio is 1.5-2.5.

[0041] The internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-heat-insulating, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film of the present invention is suitable for preparing covering materials for agricultural facilities.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] (1) The seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-lasting drip-and-fog-eliminating greenhouse film of the present invention has a width of more than 8m and a thickness of 0.08mm-0.15mm; a light transmittance of more than 90%, a haze of less than 16%; an infrared transmittance of less than 20%, which significantly improves the thermal insulation performance of the greenhouse at night; the ratio of light intensity inside and outside the greenhouse is still greater than 88% after 600 days of film covering; the dust-proof function makes the annual attenuation rate of light transmittance less than 1.1%; the drip-and-fog-eliminating function lasts for 24 months, which is synchronized with the life of the film. It can fully meet the requirements of farmers for various performance indicators of additive greenhouse films within a service life of 2 years, save more greenhouse covering costs, and be more low-carbon and green and environmentally friendly.

[0044] (2) The internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-insulating, pesticide-resistant, long-lasting drip and fog-eliminating greenhouse film described in the present invention has an innovative design scheme for guiding the drip agent to precipitate out of the inner layer in the outer three layers, that is, a high-density metallocene resin is added to the hydrotalcite thermal insulation masterbatch to increase the density of this layer to play a role in blocking the outward migration of the drip agent, which is beneficial to prolonging the drip retention effect; a high-VA content EVA resin and thermal insulation masterbatch composite system is preferably selected in the middle layer and the inner three layers to facilitate the storage of sufficient amount of drip agent and to construct a complete drip agent concentration gradient; EVA resins with different VA contents are used in the inner two layers and the inner one layer to enable them to play a role in controlling the sustained release of the drip and fog-eliminating agent, thereby achieving the excellent drip and fog-eliminating function of the internally added greenhouse film for 24 months.

[0045] (3) The internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-lasting dripping and fog-eliminating greenhouse film described in the present invention has the function of adjusting and converting the transmitted light waves, thereby realizing the precise optimization of the crop lighting environment. According to the light quality requirements of crops, chlorophyll a-mainly absorbs blue-violet light at 418nm and red light at 660nm; chlorophyll b-mainly absorbs blue light at 454nm and red light at 643nm; β-carotene-mainly absorbs blue-violet light at 400nm-500nm. The preferred light conversion agents are green-to-red GTR-650, purple-to-blue VTB440 and purple-to-red VTR660, which can be selected or compounded, so that the greenhouse film can convert part of the green light excitation spectrum 500-580nm into the red light emission spectrum 650nm, which is more beneficial to plant growth, and convert part of the ultraviolet light excitation spectrum 290-370nm into the blue light emission spectrum 440nm and the red light emission spectrum 660nm, thereby enhancing the irradiation intensity of blue and red light, improving the lighting environment and light intensity ratio in the greenhouse, and enhancing photosynthetic efficiency; adding dust-proof masterbatch reduces the friction coefficient of the film surface, making the greenhouse film bright as new after being blown by wind and rain. Since the irradiation intensity of ultraviolet light UVA is reduced, crop diseases and insect pests are reduced, the use of pesticides is reduced, and fruits and vegetables can be matured early, increase production, and have good quality, it is suitable for covering and cultivating various crops.

[0046] (4) The seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-acting drip-dispersing and fog-eliminating greenhouse film described in the present invention has an acid-resistant and aging-resistant masterbatch of the seven layers of ingredients, and the hindered amine light stabilizer used is a compound of nitrogen oxide alkyl and nitrogen alkyl (NOR+NR) 2011AR, which improves the acid resistance of the greenhouse film. The acid resistance of Examples 1-5 of the present invention is significantly improved by 6 times and 3 times compared with the acid resistance of Comparative Example 5 of the present application, which is ≤500PPM and ≤100PPM.

[0047] (5) The preparation method of the internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-lasting dripping and fog-eliminating greenhouse film described in the present invention has a scientific and reasonable layered layout function, avoids the negative synergistic effects of various functional masterbatches with light-converting agents and dripping agents, has stable and reliable quality, and is simple and easy to operate. DETAILED DESCRIPTION

[0048] The present invention is further described below with reference to the embodiments.

[0049] Example 1

[0050] The seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-acting drip-and-fog-eliminating greenhouse film of internal addition type described in Example 1 is composed of an outer layer 1, an outer layer 2, an outer layer 3, a middle layer, an inner layer 3, an inner layer 2 and an inner layer 1; wherein the outer layer 1 is a dust-proof and aging-resistant layer, and the outer layer 1 is composed of the following raw materials by mass percentage: 80% of metallocene linear low-density polyethylene (mLLDPE), 10% of acid-resistant and aging-resistant masterbatch, and 10% of dust-proof masterbatch; the outer layer 2 is a light-converting and aging-resistant layer, and the outer layer 2 is composed of the following raw materials by mass percentage. Composition: 21% low-density polyethylene (LDPE), 15% linear low-density polyethylene (LLDPE), 45% metallocene linear low-density polyethylene (mLLDPE), 8% acid-resistant and aging-resistant masterbatch, 11% light-conversion masterbatch; the outer three layers are barrier, heat-insulating, acid-resistant and aging-resistant layers. In terms of mass percentage, the outer three layers are composed of the following raw materials: 15% low-density polyethylene (LDPE), 63% metallocene linear low-density polyethylene (mLLDPE), 10% acid-resistant and aging-resistant masterbatch, 12% heat-insulating masterbatch. %; the middle layer is a high thermal insulation and acid-resistant dripping agent reserve layer, which is composed of the following raw materials by mass percentage: 62% ethylene-vinyl acetate copolymer resin (EVA), 8% acid-resistant and aging-resistant masterbatch, 20% dripping masterbatch, and 10% thermal insulation masterbatch; the inner three layers are high thermal insulation and acid-resistant dripping agent reserve layers, which are composed of the following raw materials by mass percentage: 65% ethylene-vinyl acetate copolymer resin (EVA), 9% acid-resistant and aging-resistant masterbatch, 17% dripping masterbatch, and 9% thermal insulation masterbatch; the inner two layers are high thermal insulation The temperature-resistant acid dripping and defogging agent sustained-release layer, calculated by mass percentage, the inner 2 layers are composed of the following raw materials: 67.5% ethylene-vinyl acetate copolymer resin (EVA), 10% acid-resistant and aging-resistant masterbatch, 15% dripping masterbatch, 1.5% defogging masterbatch, and 6% thermal insulation masterbatch; the inner 1 layer is the acid-resistant dripping and defogging agent release layer, calculated by mass percentage, the inner 1 layer is composed of the following raw materials: 78% ethylene-vinyl acetate copolymer resin (EVA), 9% acid-resistant and aging-resistant masterbatch, 12% dripping masterbatch, and 1% defogging masterbatch.

[0051] The raw materials for the outer layer 1 are: metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 1.0 g / 10 min, brand 2010MA, manufactured by ExxonMobil; acid-resistant and aging-resistant masterbatch (self-made); and dust-proof masterbatch brand EFT997, manufactured by Tianjin Riken Co., Ltd.

[0052] The acid-resistant and aging-resistant masterbatch in the outer layer of raw materials includes: 45% low-density polyethylene (LDPE), 40% powdered linear low-density polyethylene (LLDPE), 13% NOR+NR compound light stabilizer, and 2% antioxidant; among them: the brand of low-density polyethylene (LDPE) is 2102TN00, manufactured by Qilu Petrochemical; the brand of powdered low-density linear polyethylene (LLDPE) is 7042, manufactured by Qilu Petrochemical; the brand of light stabilizer is 2011AR, manufactured by BASF; the brand of antioxidant is B215, manufactured by Tianjin Lianlong Company.

[0053] The preparation method of the acid-resistant and aging-resistant masterbatch is as follows: low-density polyethylene (LDPE) 2102TN00, powdered linear low-density polyethylene (LLDPE) 7042, light stabilizer 2011AR and antioxidant B215 are accurately weighed and added into an internal mixer for kneading and plasticization, and then fed into a single-screw extruder granulator through an open mixer, and then hot pelletized and air-cooled and dried to obtain the acid-resistant and aging-resistant masterbatch.

[0054] Wherein: the temperature of the internal mixer is 136±1°C, the plasticizing time is 19±1 minutes, the temperature of each section of the open mixer and the single-screw granulator is 140-170°C (the first zone is 170°C, the second zone is 160°C, and the third zone is 140°C).

[0055] Among the raw materials of the outer two layers: low-density polyethylene (LDPE) with a melt index (MI) of 0.25 g / 10 min, brand 2420D, manufactured by Daqing Petrochemical; linear low-density polyethylene (LLDPE), with a melt index (MI) of 0.85 g / 10 min, brand 9085, manufactured by Tianjin Lianhua; metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 1.0 g / 10 min, brand 1018MA, manufactured by ExxonMobil; acid-resistant and aging-resistant masterbatch (self-made), and light-conversion masterbatch (self-made).

[0056] The raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch are exactly the same as those of the outer layer.

[0057] In terms of mass percentage, the light conversion masterbatch in the outer two layers is composed of the following raw materials: 45% low-density polyethylene (LDPE), 39.6% linear low-density polyethylene (LLDPE), 15% light conversion agent, and 0.4% antioxidant; among which: low-density polyethylene (LDPE) 2102TN00 is manufactured by Qilu Petrochemical; powdered linear low-density polyethylene (LLDPE) 7042 is manufactured by Qilu Petrochemical; the light conversion agent is a compound of green-to-red GTR-650Ⅱ and GTR-650Ⅲ in a mass ratio of 1:1, manufactured by Hunan Xiweier Technology Co., Ltd., and the antioxidant B215 is manufactured by Tianjin Lianlong.

[0058] The preparation method of the light conversion masterbatch is as follows: accurately weighing low-density polyethylene (LDPE) 2102TN00, powdered linear low-density polyethylene (LLDPE) 7042, a compound of light conversion agents green to red GTR-650Ⅱ and GTR-650Ⅲ, and antioxidant B215 into an internal mixer for kneading and plasticization, and then feeding the mixture into a single-screw extruder granulator through an open mixer, hot pelletizing, and air cooling and drying to obtain the light conversion masterbatch for use.

[0059] The temperature of the internal mixer is 137±1°C, the plasticizing time is 20 minutes, and the temperature of each section is 140-170°C (170°C in zone 1, 160°C in zone 2, and 140°C in zone 3).

[0060] Among the raw materials of the outer three layers: low-density polyethylene (LDPE) with a melt index (MI) of 0.25 g / 10 min, brand 2420D manufactured by Daqing Petrochemical; metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 0.5 g / 10 min, brand 2705MC manufactured by ExxonMobil.

[0061] The raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the outer three layers are exactly the same as those of the outer one layer.

[0062] In terms of mass percentage, the thermal insulation masterbatch in the outer three layers is composed of the following raw materials: 20% low-density polyethylene (LDPE), 16% linear low-density polyethylene (LLDPE), 60% hydrotalcite thermal insulation agent, 2.0% coupling agent, 1.0% lubricant, and 1.0% dispersant; wherein: the melt index (MI) of the low-density polyethylene (LDPE) is 2.0g / 10min, and the grade produced by Qilu Petrochemical is 2102TN00; the melt index (MI) of the linear low-density polyethylene (LLDPE) is 2.0g / 10min, and the appearance is powder, which is the grade 7042 produced by Qilu Petrochemical; the hydrotalcite thermal insulation agent, the grade is HTP, manufactured by Sakai Chemical Co., Ltd. of Japan; the coupling agent is aluminate, produced by Qingdao Jisi Company; the lubricant is a mixture of zinc stearate and calcium stearate produced by Hebei Zhongshang Chemical in a mass ratio of 1:1; the dispersant is polyethylene wax.

[0063] The preparation method of the thermal insulation masterbatch is:

[0064] Low-density polyethylene (LDPE) 2102TN00, linear low-density polyethylene (LLDPE) 7042, hydrotalcite thermal insulation agent HTP, aluminate coupling agent, zinc stearate and calcium stearate mixed lubricant and polyethylene wax dispersant are accurately measured and added into an internal mixer for kneading and plasticization, and then fed into a single-screw extruder granulator through an open mixer, and then hot pelletized and air-cooled and dried to obtain a thermal insulation masterbatch for use.

[0065] The temperature of the internal mixer is 137±1°C, the plasticizing time is 19±1 minutes, and the temperature of each section is 140-170°C (170°C in the first zone, 160°C in the second zone, and 140°C in the third zone).

[0066] The raw materials of the middle layer include: ethylene-vinyl acetate copolymer resin (EVA), VA content of 19%, melt index (MI) of 0.65g / 10min, brand 00119, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the middle layer are exactly the same as those of the outer layer 1; the raw material composition and preparation method of the thermal insulation masterbatch in the middle layer are exactly the same as those of the outer 3 layers.

[0067] In terms of mass percentage, the drip masterbatch of the middle layer is composed of the following raw materials: 40% ethylene vinyl acetate (EVA) resin, 33.5% linear low density polyethylene (LLDPE), 20% drip agent, 0.5% antioxidant, and 6% ultrafine silicon dioxide.

[0068] Wherein: the melt index (MI) of the ethylene-vinyl acetate (EVA) resin in the drip masterbatch is 2.0 g / 10 min, and the VA content is 14% and the grade is 14-2 produced by Beijing Yanshan Organic Chemical; the melt index (MI) of the linear low-density polyethylene (LLDPE) is 2.0 g / 10 min, and the appearance is powder, and the linear low-density polyethylene (LLDPE) is 7042 produced by Qilu Petrochemical; the drip agent grade LD777 is a polyol borate drip agent, produced by Qingdao Siwei Chemical; the antioxidant is B215, and the manufacturer is Tianjin Lianlong Company; the ultrafine silica is produced by Foshan Jinchun and the grade is J430.

[0069] The preparation method of the drip masterbatch is as follows: ethylene vinyl acetate (EVA) resin, linear low-density polyethylene (LLDPE), drip agent, antioxidant and ultrafine silica are added into a high-speed mixer according to proportion and kneaded, and then the kneaded material is fed into a twin-screw extruder granulator, and the drip masterbatch is obtained after drawing, water cooling, pelletizing, drying and cooling.

[0070] Wherein: the temperature of the high-speed mixer is 80°C, the kneading time is 13 minutes, and the temperature of the twin-screw extruder granulator is 150-175°C, wherein: zone 1 is 150°C, zone 2 is 165°C, zone 3 is 175°C, and zone 4 is 175°C.

[0071] The raw materials of the inner three layers are: ethylene-vinyl acetate copolymer resin (EVA), VA content 14%, melt index (MI) 0.25g / 10min, brand FL00014, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the inner three layers are exactly the same as those of the outer one layer; the raw material composition and preparation method of the thermal insulation masterbatch in the inner three layers are exactly the same as those of the outer three layers. The raw material composition and preparation method of the drip masterbatch in the inner three layers are exactly the same as those of the middle layer.

[0072] The raw materials of the inner 2 layers are: ethylene-vinyl acetate copolymer resin (EVA), VA content 12%, melt index (MI) 0.5g / 10min, brand FL00012, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the inner 2 layers are exactly the same as those of the outer 1 layer; the raw material composition and preparation method of the thermal insulation masterbatch in the inner 2 layers are exactly the same as those of the outer 3 layers. The raw material composition and preparation method of the drip masterbatch in the inner 2 layers are exactly the same as those of the middle layer.

[0073] Calculated by mass percentage, the defogging masterbatch in the inner two layers is composed of the following raw materials: 50% ethylene vinyl acetate (EVA) resin, 39.8% linear low-density polyethylene (LLDPE), 10% defogging agent, and 0.2% antioxidant.

[0074] Among them: the melt index (MI) of the ethylene-vinyl acetate (EVA) resin in the defogging masterbatch is 2.0g / 10min, and the VA content is 14% and the grade is 14-2 produced by Beijing Yanshan Organic Chemical; the melt index (MI) of the linear low-density polyethylene (LLDPE) is 2.0g / 10min, and the linear low-density polyethylene (LLDPE) is 7042 produced by Qilu Petrochemical; the defogging agent TS403 is produced by Dalian Jinlong; the antioxidant is B215 produced by Tianjin Lianlong Company.

[0075] The preparation method of the defogging masterbatch is as follows: ethylene vinyl acetate (EVA) resin, linear low-density polyethylene (LLDPE), defogging agent and antioxidant are added into a high-speed mixer according to proportion and kneaded, and then the kneaded material is fed into a twin-screw extruder granulator, and then the defogging masterbatch is obtained after being drawn, water-cooled, pelletized, and entered into a drying device and cooled.

[0076] Wherein: the temperature of the high-speed mixer is 80°C, the kneading time is 13 minutes, and the temperature of the twin-screw extruder granulator is 150-175°C, wherein: zone 1 is 150°C, zone 2 is 165°C, zone 3 is 175°C, and zone 4 is 175°C.

[0077] The raw materials of the inner layer 1 are: ethylene-vinyl acetate copolymer resin (EVA), VA content 7.5%, melt index (MI) 0.5g / 10min, brand 00111, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the inner layer 1 are exactly the same as those of the outer layer 1. The raw material composition and preparation method of the drip masterbatch in the inner layer 1 are exactly the same as those of the middle layer. The raw material composition and preparation method of the defogging masterbatch in the inner layer 1 are exactly the same as those of the inner layer 2.

[0078] The preparation method of the internally added polyolefin seven-layer co-extruded light-converting dust-proof, high thermal insulation, pesticide resistance and long-acting dripping and fog-eliminating shed film described in this embodiment 1 is: the component materials of the outer 1 layer, the outer 2 layers, the outer 3 layers, the middle layer, the inner 3 layers, the inner 2 layers and the inner 1 layer are respectively mixed and stirred evenly, and added into a seven-layer co-extruder, and subjected to melt plasticization blow molding, cooling and shaping, traction, corona, coating liquid impregnation, drying, edge welding, seam slitting, coding and marking, and winding to obtain the internally added polyolefin seven-layer co-extruded light-converting dust-proof, high thermal insulation, pesticide resistance and long-acting dripping and fog-eliminating shed film.

[0079] The product specification is 12000 / 0.12mm, with a designed service life of 2 years; the thickness ratio of outer 1 layer, outer 2 layers, outer 3 layers, middle layer, inner 3 layers, inner 2 layers and inner 1 layer is 1:1:1:1:1:1:1; the blowing ratio is 1.75. In the seven-layer co-extrusion unit, the process conditions of the inner 1 layer, inner 2 layers, inner 3 layers, middle layer, outer 3 layers, outer 2 layers and outer 1 layer extruder, machine neck, die head, die head bottom and die ring temperature, and the temperature of each zone of the oven are set as shown in Table 1.

[0080] Table 1 Preparation process conditions of Example 1

[0081]

[0082]

[0083] The internally added polyolefin seven-layer co-extruded light-converting dust-proof high-insulation pesticide-resistant long-acting drip-removing fog-removing greenhouse film prepared in Example 1 has a light transmittance of 90.3%, a haze of 15.2%, and a duration of drip-removing fog-removing function of 2 years. The addition of the light-converting agent GTR650 enables the greenhouse film to have the function of converting part of the green light excitation spectrum of 580nm into the red light emission spectrum of 650nm, which is more beneficial to plant growth, and improves the lighting environment in the greenhouse, so that the fruit is colored quickly, the vitamin C content is high, and the taste quality is good; the addition of dust-proof masterbatch reduces the friction coefficient of the greenhouse film surface to 0.10, and it is as bright as new after being blown by wind and washed by rain, and the light transmittance attenuation is not obvious; the addition of high-insulation resin EVA and insulation masterbatch acts as a carrier for the storage and sustained release of dripping agent, and makes the transmittance of infrared radiation outward from the greenhouse at night low. The greenhouse film prepared in Example 1 has been planted at the Shandong Agricultural University Experimental Base in Lujiazhuang, Fangxia Town, Laiwu in October 2022, covering sweet peppers (Caitlin), with a yield increase of 27.6% and harvesting 7 days earlier. The greenhouse film prepared in Example 1 was determined by experts to be a special film for sweet peppers. After the demonstration and verification of the greenhouse, Example 1 is also suitable for covering crops such as eggplant, zucchini, Queen Nina and Clenson grapes.

[0084] Example 2

[0085] The internally added polyolefin seven-layer co-extruded light-converting dust-proof high-insulation pesticide-resistant long-acting drip-and-fog-eliminating shed film described in Example 2 is composed of an outer layer 1, an outer layer 2, an outer layer 3, a middle layer, an inner layer 3, an inner layer 2 and an inner layer 1; wherein the outer layer 1 is a dust-proof and aging-resistant layer, and in terms of mass percentage, the outer layer 1 is composed of the following raw materials: 82% of metallocene linear low-density polyethylene (mLLDPE), 9% of acid-resistant and aging-resistant masterbatch, and 9% of dust-proof masterbatch; the outer layer 2 is a light-converting and aging-resistant layer, and in terms of mass percentage, the outer layer 2 is composed of the following raw materials The outer three layers are composed of the following raw materials: low-density polyethylene (LDPE) 23%, linear low-density polyethylene (LLDPE) 17%, metallocene linear low-density polyethylene (mLLDPE) 40%, acid-resistant and aging-resistant masterbatch 10%, and light-converting masterbatch 10%; the outer three layers are barrier, heat-insulating, acid-resistant and aging-resistant layers. In terms of mass percentage, the outer three layers are composed of the following raw materials: low-density polyethylene (LDPE) 20%, metallocene linear low-density polyethylene (mLLDPE) 60%, acid-resistant and aging-resistant masterbatch 9%, and heat-insulating masterbatch 11 %; the middle layer is a high thermal insulation and acid-resistant dripping agent reserve layer, which is composed of the following raw materials by mass percentage: ethylene-vinyl acetate copolymer resin (EVA) 62%, acid-resistant and aging-resistant masterbatch 9%, dripping masterbatch 20%, and thermal insulation masterbatch 9%; the inner 3 layers are high thermal insulation and acid-resistant dripping agent reserve layers, which are composed of the following raw materials by mass percentage: ethylene-vinyl acetate copolymer resin (EVA) 66%, acid-resistant and aging-resistant masterbatch 8%, dripping masterbatch 17%, and thermal insulation masterbatch 9%; the inner 2 layers are high thermal insulation The temperature-resistant acid dripping and defogging agent sustained-release layer, calculated by mass percentage, the inner 2 layers are composed of the following raw materials: 68.5% ethylene-vinyl acetate copolymer resin (EVA), 9% acid-resistant and aging-resistant masterbatch, 14% dripping masterbatch, 1.5% defogging masterbatch, and 7% thermal insulation masterbatch; the inner 1 layer is the acid-resistant dripping and defogging agent release layer, calculated by mass percentage, the inner 1 layer is composed of the following raw materials: 79% ethylene-vinyl acetate copolymer resin (EVA), 9% acid-resistant and aging-resistant masterbatch, 11% dripping masterbatch, and 1% defogging masterbatch.

[0086] The raw materials for the outer layer 1 are: metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 1.0 g / 10 min, brand 2010MA, manufactured by ExxonMobil; acid-resistant and aging-resistant masterbatch (self-made); and dust-proof masterbatch brand EFT997, manufactured by Tianjin Riken Co., Ltd.

[0087] The raw material composition and preparation process of the acid-resistant and aging-resistant masterbatch are exactly the same as those of the outer layer 1 in Example 1.

[0088] Among the raw materials of the outer two layers: low-density polyethylene (LDPE) with a melt index (MI) of 0.25 g / 10 min, brand 2420D, manufactured by Daqing Petrochemical; linear low-density polyethylene (LLDPE), with a melt index (MI) of 0.85 g / 10 min, brand 9085, manufactured by Tianjin Lianhua; metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 1.0 g / 10 min, brand 1018MA, manufactured by ExxonMobil; acid-resistant and aging-resistant masterbatch (self-made), and light-conversion masterbatch (self-made).

[0089] The raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch are exactly the same as those of the outer layer 1 in Example 1.

[0090] In terms of mass percentage, the light conversion masterbatch in the outer two layers is composed of the following raw materials: 45% low-density polyethylene (LDPE), 39.6% linear low-density polyethylene (LLDPE), 15% light conversion agent, and 0.4% antioxidant; among them: low-density polyethylene (LDPE) 2102TN00 is manufactured by Qilu Petrochemical; powdered linear low-density polyethylene (LLDPE) 7042 is manufactured by Qilu Petrochemical; the light conversion agent is green-to-red GTR-650Ⅱ and GTR-650Ⅲ, purple-to-red VTR660, and purple-to-blue VTB440, which are compounded in a mass ratio of 3:2:2:3 and manufactured by Hunan Xiweier Technology Co., Ltd., and the antioxidant B215 is manufactured by Tianjin Lianlong.

[0091] The preparation method of the light conversion masterbatch is exactly the same as that of the outer two layers in Example 1.

[0092] Among the raw materials of the outer three layers: low-density polyethylene (LDPE) with a melt index (MI) of 0.25 g / 10 min, brand 2420D manufactured by Daqing Petrochemical; metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 0.5 g / 10 min, brand 2705MC manufactured by ExxonMobil.

[0093] The raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the outer three layers are exactly the same as those of the outer one layer in Example 1.

[0094] The raw material composition and preparation method of the thermal insulation masterbatch in the outer three layers are exactly the same as those of the outer three layers in Example 1.

[0095] The raw materials of the middle layer include: ethylene-vinyl acetate copolymer resin (EVA), VA content 19%, melt index (MI) 0.65g / 10min, brand 00119, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the middle layer are exactly the same as those of the outer layer 1 in Example 1; the raw material composition and preparation method of the thermal insulation masterbatch in the middle layer are exactly the same as those of the outer 3 layers in Example 1. The raw material composition and preparation method of the drip masterbatch in the middle layer are exactly the same as those of the middle layer in Example 1.

[0096] The raw materials of the inner three layers are: ethylene-vinyl acetate copolymer resin (EVA), VA content 14%, melt index (MI) 0.25g / 10min, brand FL00014, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the inner three layers are exactly the same as those of the outer one layer in Example 1; the raw material composition and preparation method of the thermal insulation masterbatch in the inner three layers are exactly the same as those of the outer three layers in Example 1. The raw material composition and preparation method of the drip masterbatch in the inner three layers are exactly the same as those of the middle layer in Example 1.

[0097] The raw materials of the inner 2 layers: ethylene-vinyl acetate copolymer resin (EVA), VA content of 12%, melt index (MI) of 0.5g / 10min, brand FL00012, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the inner 2 layers are exactly the same as those of the outer 1 layer in Example 1; the raw material composition and preparation method of the thermal insulation masterbatch in the inner 2 layers are exactly the same as those of the outer 3 layers in Example 1. The raw material composition and preparation method of the drip masterbatch in the inner 2 layers are exactly the same as those of the middle layer in Example 1. The raw material composition and preparation method of the defogging masterbatch in the inner 2 layers are exactly the same as those of the inner 2 layers in Example 1.

[0098] The raw materials of the inner layer 1 are: ethylene-vinyl acetate copolymer resin (EVA), VA content 7.5%, melt index (MI) 0.5g / 10min, brand 00111, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the inner layer 1 are exactly the same as those of the outer layer 1 in Example 1. The raw material composition and preparation method of the drip masterbatch in the inner layer 1 are exactly the same as those of the middle layer in Example 1. The raw material composition and preparation method of the defogging masterbatch in the inner layer 1 are exactly the same as those of the inner 2 layers in Example 1.

[0099] The preparation method and process conditions of the internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film described in this Example 2 are exactly the same as those in Example 1.

[0100] The seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-lasting dripping and fog-eliminating greenhouse film prepared in Example 2 has a product specification of 12000 / 0.12mm and a designed service life of 2 years. The light transmittance is 90.7%, the haze is 15.7%, and the dripping and fog-eliminating function lasts for 24 months after the greenhouse buckle verification. The addition of light conversion agents such as green-to-red GTR-650Ⅱ+Ⅲ, purple-to-blue VTB440 and purple-to-red VTR660 makes the greenhouse film have the function of converting part of the green light excitation spectrum 500-580nm into the red light emission spectrum 650nm which is more beneficial to plant growth, and converting part of the ultraviolet light excitation spectrum 290-370nm into the blue light emission spectrum 440nm and the red light emission spectrum 660nm, which enhances the irradiation intensity of blue and red light, improves the lighting environment in the greenhouse, increases the vitamin C content, has good coloring and high yield; the addition of dust-proof masterbatch makes the greenhouse film bright as new after being blown by wind and rain, and the light transmittance does not decrease significantly. The addition of high thermal insulation resin EVA and thermal insulation masterbatch acts as a drip agent reserve and slow-release carrier, and makes the transmittance of infrared radiation from the greenhouse to the outside at night low. The greenhouse film prepared in Example 2 was applied in the field demonstration at the Shandong Agricultural University Experimental Base in Gaozhuang, Fangxia Town, Laiwu in October 2022. The strawberry (Sweet Treasure) planted increased its yield by 25.60%, and was picked 9 days in advance. The fruit was large and red, with a high taste, sugar content and high quality. The greenhouse film prepared in Example 2 was evaluated by experts as a special film for strawberries. It is also suitable for covering the planting of cherries, blueberries, etc.

[0101] Example 3

[0102] The internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-acting dripping and fog-eliminating shed film described in Example 3 is composed of an outer layer 1, an outer layer 2, an outer layer 3, a middle layer, an inner layer 3, an inner layer 2 and an inner layer 1; wherein the outer layer 1 is a dust-proof and aging-resistant layer, and in terms of mass percentage, the outer layer 1 is composed of the following raw materials: 83% of metallocene linear low-density polyethylene (mLLDPE), 9% of acid-resistant and aging-resistant masterbatch, and 8% of dust-proof masterbatch; the outer layer 2 is a light-converting and aging-resistant layer, and in terms of mass percentage, the outer layer 2 is composed of the following raw materials Composition: low-density polyethylene (LDPE) 25%, linear low-density polyethylene (LLDPE) 15%, metallocene linear low-density polyethylene (mLLDPE) 42%, acid-resistant and aging-resistant masterbatch 9%, light-conversion masterbatch 9%; the outer three layers are barrier, heat-insulating, acid-resistant and aging-resistant layers. In terms of mass percentage, the outer three layers are composed of the following raw materials: low-density polyethylene (LDPE) 22%, metallocene linear low-density polyethylene (mLLDPE) 60%, acid-resistant and aging-resistant masterbatch 8%, and heat-insulating masterbatch 10%; The middle layer is a high thermal insulation and acid-resistant dripping agent reserve layer. In terms of mass percentage, the middle layer is composed of the following raw materials: 60% ethylene-vinyl acetate copolymer resin (EVA), 10% acid-resistant and aging-resistant masterbatch, 20% dripping masterbatch, and 10% thermal insulation masterbatch; the inner three layers are high thermal insulation and acid-resistant dripping agent reserve layers. In terms of mass percentage, the inner three layers are composed of the following raw materials: 63% ethylene-vinyl acetate copolymer resin (EVA), 9% acid-resistant and aging-resistant masterbatch, 18% dripping masterbatch, and 10% thermal insulation masterbatch; the inner two layers are high The thermal insulation, acid-resistant, dripping and defogging agent sustained-release layer is composed of the following raw materials, calculated by mass percentage, for the inner two layers: 69.5% ethylene-vinyl acetate copolymer resin (EVA), 8% acid-resistant and aging-resistant masterbatch, 15% dripping masterbatch, 1.5% defogging masterbatch, and 6% thermal insulation masterbatch; the inner 1 layer is the acid-resistant, dripping and defogging agent release layer, calculated by mass percentage, for the inner 1 layer is composed of the following raw materials: 80% ethylene-vinyl acetate copolymer resin (EVA), 8% acid-resistant and aging-resistant masterbatch, 11% dripping masterbatch, and 1% defogging masterbatch.

[0103] The raw materials for the outer layer 1 are: metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 1.0 g / 10 min, brand 2010MA, manufactured by ExxonMobil; acid-resistant and aging-resistant masterbatch (self-made); and dust-proof masterbatch brand EFT997, manufactured by Tianjin Riken Co., Ltd.

[0104] The raw material composition and preparation process of the acid-resistant and aging-resistant masterbatch are exactly the same as those of the outer layer 1 in Example 1.

[0105] Among the raw materials of the outer two layers: the melt index (MI) of low-density polyethylene (LDPE) is 0.25g / 10min, the brand is 2420D, manufactured by Daqing Petrochemical; the linear low-density polyethylene (LLDPE) has a melt index (MI) of 0.85g / 10min, the brand is 9085, manufactured by Tianjin Lianhua; the metallocene linear low-density polyethylene (m-LLDPE) has a melt index (MI) of 1.0g / 10min, the brand is 1018MA, manufactured by ExxonMobil; acid-resistant and aging-resistant masterbatch (self-made), light-conversion masterbatch (self-made); the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch are exactly the same as those of the outer layer of Example 1.

[0106] In terms of mass percentage, the light conversion masterbatch in the outer two layers is composed of the following raw materials: 45% low-density polyethylene (LDPE), 39.6% linear low-density polyethylene (LLDPE), 15% light conversion agent, and 0.4% antioxidant; among which: low-density polyethylene (LDPE) 2102TN00 is manufactured by Qilu Petrochemical; powdered linear low-density polyethylene (LLDPE) 7042 is manufactured by Qilu Petrochemical; the light conversion agent is green-to-red GTR-650Ⅱ and GTR-650Ⅲ, purple-to-red VTR660, and purple-to-blue VTB440, compounded in a mass ratio of 3:3:2:2, manufactured by Hunan Xiweier Technology Co., Ltd., and the antioxidant B215 is manufactured by Tianjin Lianlong.

[0107] The preparation method of the light conversion masterbatch is exactly the same as that of the outer two layers in Example 1.

[0108] Among the raw materials of the outer three layers: low-density polyethylene (LDPE) with a melt index (MI) of 0.25 g / 10 min, brand 2420D manufactured by Daqing Petrochemical; metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 0.5 g / 10 min, brand 2705MC manufactured by ExxonMobil. The raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the outer three layers are exactly the same as those of the outer layer 1 in Example 1. The raw material composition and preparation method of the thermal insulation masterbatch in the outer three layers are exactly the same as those of the outer three layers in Example 1.

[0109] The raw materials of the middle layer: ethylene-vinyl acetate copolymer resin (EVA), VA content 19%, melt index (MI) 0.65g / 10min, brand 00119, produced by ExxonMobil; drip masterbatch brand EFT641 (drip agent KF650 content 20%), manufactured by Tianjin Riken Kaisha; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the middle layer are exactly the same as those of the outer layer 1 in Example 1; the raw material composition and preparation method of the thermal insulation masterbatch in the middle layer are exactly the same as those of the outer 3 layers in Example 1. The raw material composition and preparation method of the drip masterbatch in the middle layer are exactly the same as those of the middle layer in Example 1.

[0110] The raw materials of the inner three layers are: ethylene-vinyl acetate copolymer resin (EVA), VA content 14%, melt index (MI) 0.25g / 10min, brand FL00014, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the inner three layers are exactly the same as those of the outer one layer in Example 1; the raw material composition and preparation method of the thermal insulation masterbatch in the inner three layers are exactly the same as those of the outer three layers in Example 1. The raw material composition and preparation method of the drip masterbatch in the inner three layers are exactly the same as those of the middle layer in Example 1.

[0111] The raw materials of the inner 2 layers: ethylene-vinyl acetate copolymer resin (EVA), VA content of 12%, melt index (MI) of 0.5g / 10min, brand FL00012, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the inner 2 layers are exactly the same as those of the outer 1 layer in Example 1; the raw material composition and preparation method of the thermal insulation masterbatch in the inner 2 layers are exactly the same as those of the outer 3 layers in Example 1. The raw material composition and preparation method of the drip masterbatch in the inner 2 layers are exactly the same as those of the middle layer in Example 1. The raw material composition and preparation method of the defogging masterbatch in the inner 2 layers are exactly the same as those of the inner 2 layers in Example 1.

[0112] The raw materials of the inner layer 1 are: ethylene-vinyl acetate copolymer resin (EVA), VA content 7.5%, melt index (MI) 0.5g / 10min, brand 00111, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the inner layer 1 are exactly the same as those of the outer layer 1 in Example 1. The raw material composition and preparation method of the drip masterbatch in the inner layer 1 are exactly the same as those of the middle layer in Example 1. The raw material composition and preparation method of the defogging masterbatch in the inner layer 1 are exactly the same as those of the inner 2 layers in Example 1.

[0113] The preparation method and process conditions of the internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film described in Example 3 are exactly the same as those in Example 1.

[0114] The seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-lasting dripping and fog-eliminating greenhouse film prepared in Example 3 has a product specification of 12000 / 0.12mm and a designed service life of 2 years. The light transmittance is 90.5%, the haze is 15.6%, and the duration of the dripping and fog-eliminating function is 24 months after the greenhouse buckle verification. The addition of light conversion agents such as green-to-red GTR-650Ⅱ+Ⅲ, purple-to-blue VTB440 and purple-to-red VTR660 makes the greenhouse film have the function of converting part of the green light excitation spectrum 500-580nm into the red light emission spectrum 650nm which is more beneficial to plant growth, and converting part of the ultraviolet light excitation spectrum 290-370nm into the blue light emission spectrum 440nm and the red light emission spectrum 660nm, which enhances the irradiation intensity of blue and red light, improves the lighting environment in the greenhouse, increases the vitamin C content, has good coloring and high yield; the addition of dust-proof masterbatch makes the greenhouse film bright as new after being blown by wind and rain, and the light transmittance does not decrease significantly. The addition of high thermal insulation resin EVA and thermal insulation masterbatch acts as a drip agent reserve and slow-release carrier, and makes the transmittance of infrared radiation from the greenhouse to the outside at night low. The greenhouse film prepared in Example 3 was applied in the field demonstration at the Shandong Agricultural University Experimental Base in Gaozhuang, Fangxia Town, Laiwu in October 2022. The tomato (Pioneer 4) planted increased its yield by 25.30%, and was picked 7 days in advance. The fruit was large and red, with a high taste and sugar content. The greenhouse film prepared in this Example 3 was evaluated by experts as a special film for tomatoes. It is also suitable for covering the planting of cucumbers, bitter gourds, melons, watermelons, winter dates, etc.

[0115] Example 4

[0116] The internally added polyolefin seven-layer co-extruded light-converting dust-proof high-insulation pesticide-resistant long-acting drip-and-fog-eliminating shed film described in Example 4 is composed of an outer layer 1, an outer layer 2, an outer layer 3, a middle layer, an inner layer 3, an inner layer 2 and an inner layer 1; wherein the outer layer 1 is a dust-proof and aging-resistant layer, and the outer layer 1 is composed of the following raw materials by mass percentage: 84% of metallocene linear low-density polyethylene (mLLDPE), 8% of acid-resistant and aging-resistant masterbatch, and 8% of dust-proof masterbatch; the outer layer 2 is a light-converting and aging-resistant layer, and the outer layer 2 is composed of the following raw materials by mass percentage The outer three layers are composed of the following raw materials: low-density polyethylene (LDPE) 28%, linear low-density polyethylene (LLDPE) 16%, metallocene linear low-density polyethylene (mLLDPE) 35%, acid-resistant and aging-resistant masterbatch 11%, and light-conversion masterbatch 10%; the outer three layers are barrier, heat-insulating, acid-resistant and aging-resistant layers. In terms of mass percentage, the outer three layers are composed of the following raw materials: low-density polyethylene (LDPE) 18%, metallocene linear low-density polyethylene (mLLDPE) 62%, acid-resistant and aging-resistant masterbatch 10%, and heat-insulating masterbatch 10 %; the middle layer is a high thermal insulation and acid-resistant dripping agent reserve layer, which is composed of the following raw materials by mass percentage: ethylene-vinyl acetate copolymer resin (EVA) 59%, acid-resistant and aging-resistant masterbatch 9%, dripping masterbatch 21%, and thermal insulation masterbatch 11%; the inner three layers are high thermal insulation and acid-resistant dripping agent reserve layers, which are composed of the following raw materials by mass percentage: ethylene-vinyl acetate copolymer resin (EVA) 66%, acid-resistant and aging-resistant masterbatch 8%, dripping masterbatch 16%, and thermal insulation masterbatch 10%; the inner two layers are high The thermal insulation, acid-resistant, dripping and defogging agent sustained-release layer is composed of the following raw materials, calculated by mass percentage, for the inner two layers: 69.5% ethylene-vinyl acetate copolymer resin (EVA), 9% acid-resistant and aging-resistant masterbatch, 14% dripping masterbatch, 1.5% defogging masterbatch, and 6% thermal insulation masterbatch; the inner 1 layer is the acid-resistant, dripping and defogging agent release layer, and is composed of the following raw materials, calculated by mass percentage, for the inner 1 layer: 79% ethylene-vinyl acetate copolymer resin (EVA), 9% acid-resistant and aging-resistant masterbatch, 11% dripping masterbatch, and 1% defogging masterbatch.

[0117] The raw materials for the outer layer 1 are: metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 1.0 g / 10 min, brand 2010MA, manufactured by ExxonMobil; acid-resistant and aging-resistant masterbatch (self-made); and dust-proof masterbatch brand EFT997, manufactured by Tianjin Riken Co., Ltd.

[0118] The raw material composition and preparation process of the acid-resistant and aging-resistant masterbatch are exactly the same as those of the outer layer 1 in Example 1.

[0119] Among the raw materials of the outer two layers: low-density polyethylene (LDPE) with a melt index (MI) of 0.25 g / 10 min, brand 2420D, manufactured by Daqing Petrochemical; linear low-density polyethylene (LLDPE), with a melt index (MI) of 0.85 g / 10 min, brand 9085, manufactured by Tianjin Lianhua; metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 1.0 g / 10 min, brand 1018MA, manufactured by ExxonMobil; acid-resistant and aging-resistant masterbatch (self-made), and light-conversion masterbatch (self-made).

[0120] The raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch are exactly the same as those of the outer layer 1 in Example 1.

[0121] In terms of mass percentage, the light conversion masterbatch in the outer two layers is composed of the following raw materials: 45% low-density polyethylene (LDPE), 39.6% linear low-density polyethylene (LLDPE), 15% light conversion agent, and 0.4% antioxidant; among them: low-density polyethylene (LDPE) 2102TN00 is manufactured by Qilu Petrochemical; powdered linear low-density polyethylene (LLDPE) 7042 is manufactured by Qilu Petrochemical; the light conversion agent is green-to-red GTR-650Ⅱ and GTR-650Ⅲ, purple-to-red VTR660, and purple-to-blue VTB440, which are compounded in a mass ratio of 3:2:2:3 and manufactured by Hunan Xiweier Technology Co., Ltd., and the antioxidant B215 is manufactured by Tianjin Lianlong.

[0122] The preparation method of the light conversion masterbatch is exactly the same as that of the outer two layers in Example 1.

[0123] Among the raw materials of the outer three layers: low-density polyethylene (LDPE) with a melt index (MI) of 0.25 g / 10 min, brand 2420D manufactured by Daqing Petrochemical; metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 0.5 g / 10 min, brand 2705MC manufactured by ExxonMobil. The raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the outer three layers are exactly the same as those of the outer layer 1 in Example 1. The raw material composition and preparation method of the thermal insulation masterbatch in the outer three layers are exactly the same as those of the outer three layers in Example 1.

[0124] The raw materials of the middle layer include: ethylene-vinyl acetate copolymer resin (EVA), VA content 19%, melt index (MI) 0.65g / 10min, brand 00119, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the middle layer are exactly the same as those of the outer layer 1 in Example 1; the raw material composition and preparation method of the thermal insulation masterbatch in the middle layer are exactly the same as those of the outer 3 layers in Example 1. The raw material composition and preparation method of the drip masterbatch in the middle layer are exactly the same as those of the middle layer in Example 1.

[0125] The raw materials of the inner three layers are: ethylene-vinyl acetate copolymer resin (EVA), VA content 14%, melt index (MI) 0.25g / 10min, brand FL00014, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the inner three layers are exactly the same as those of the outer one layer in Example 1; the raw material composition and preparation method of the thermal insulation masterbatch in the inner three layers are exactly the same as those of the outer three layers in Example 1. The raw material composition and preparation method of the drip masterbatch in the inner three layers are exactly the same as those of the middle layer in Example 1.

[0126] The raw materials of the inner 2 layers: ethylene-vinyl acetate copolymer resin (EVA), VA content of 12%, melt index (MI) of 0.5g / 10min, brand FL00012, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the inner 2 layers are exactly the same as those of the outer 1 layer in Example 1; the raw material composition and preparation method of the thermal insulation masterbatch in the inner 2 layers are exactly the same as those of the outer 3 layers in Example 1. The raw material composition and preparation method of the drip masterbatch in the inner 2 layers are exactly the same as those of the middle layer in Example 1. The raw material composition and preparation method of the defogging masterbatch in the inner 2 layers are exactly the same as those of the inner 2 layers in Example 1.

[0127] The raw materials of the inner layer 1 are: ethylene-vinyl acetate copolymer resin (EVA), VA content 7.5%, melt index (MI) 0.5g / 10min, brand 00111, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the inner layer 1 are exactly the same as those of the outer layer 1 in Example 1. The raw material composition and preparation method of the drip masterbatch in the inner layer 2 are exactly the same as those of the middle layer in Example 1. The raw material composition and preparation method of the defogging masterbatch in the inner layer 2 are exactly the same as those of the inner layer 2 in Example 1.

[0128] The preparation method and process conditions of the internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film described in Example 4 are exactly the same as those in Example 1.

[0129] The seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-lasting dripping and fog-eliminating greenhouse film prepared in Example 4 has a product specification of 12000 / 0.12mm and a designed service life of 2 years. The light transmittance is 90.8%, the haze is 15.3%, and the dripping and fog-eliminating function lasts for 24 months after the greenhouse buckle verification. The addition of light conversion agents such as green-to-red GTR-650Ⅱ+Ⅲ, purple-to-blue VTB440 and purple-to-red VTR660 makes the greenhouse film have the function of converting part of the green light excitation spectrum 500-580nm into the red light emission spectrum 650nm which is more beneficial to plant growth, and converting part of the ultraviolet light excitation spectrum 290-370nm into the blue light emission spectrum 440nm and the red light emission spectrum 660nm, which enhances the irradiation intensity of blue and red light, improves the lighting environment in the greenhouse, increases the vitamin C content, has good coloring and high yield; the addition of dust-proof masterbatch makes the greenhouse film bright as new after being blown by wind and rain, and the light transmittance does not decrease significantly. The addition of high thermal insulation resin EVA and thermal insulation masterbatch acts as a drip agent reserve and slow-release carrier, and makes the transmittance of infrared radiation from the greenhouse to the outside at night low. The greenhouse film prepared in Example 4 has been applied in the Laiwu Gaozhuang greenhouse of Shandong Agricultural University in Laiwu in October 2022. The blueberry yield increased by 18.3%, and the blueberries were picked 10 days earlier. The fruits were large, bright in color, and had good taste. The greenhouse film prepared in Example 4 was evaluated by experts and determined to be a special film for blueberries.

[0130] Example 5

[0131] The internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-acting dripping and fog-eliminating shed film described in Example 5 is composed of an outer layer 1, an outer layer 2, an outer layer 3, a middle layer, an inner layer 3, an inner layer 2 and an inner layer 1; wherein the outer layer 1 is a dust-proof and aging-resistant layer, and the outer layer 1 is composed of the following raw materials by mass percentage: 83% of metallocene linear low-density polyethylene (mLLDPE), 8% of acid-resistant and aging-resistant masterbatch, and 9% of dust-proof masterbatch; the outer layer 2 is a light-converting and aging-resistant layer, and the outer layer 2 is composed of the following raw materials by mass percentage. The outer three layers are composed of the following raw materials: low-density polyethylene (LDPE) 24%, linear low-density polyethylene (LLDPE) 20%, metallocene linear low-density polyethylene (mLLDPE) 35%, acid-resistant and aging-resistant masterbatch 10%, and light-conversion masterbatch 11%; the outer three layers are barrier, heat-insulating, acid-resistant and aging-resistant layers. In terms of mass percentage, the outer three layers are composed of the following raw materials: low-density polyethylene (LDPE) 16%, metallocene linear low-density polyethylene (mLLDPE) 63%, acid-resistant and aging-resistant masterbatch 9%, and heat-insulating masterbatch 12 %; the middle layer is a high thermal insulation and acid-resistant dripping agent reserve layer, which is composed of the following raw materials by mass percentage: ethylene-vinyl acetate copolymer resin (EVA) 62%, acid-resistant and aging-resistant masterbatch 8%, dripping masterbatch 21%, and thermal insulation masterbatch 9%; the inner 3 layers are high thermal insulation and acid-resistant dripping agent reserve layers, which are composed of the following raw materials by mass percentage: ethylene-vinyl acetate copolymer resin (EVA) 65%, acid-resistant and aging-resistant masterbatch 9%, dripping masterbatch 17%, and thermal insulation masterbatch 9%; the inner 2 layers are high thermal insulation The temperature-resistant acid dripping and defogging agent sustained-release layer, calculated by mass percentage, the inner 2 layers are composed of the following raw materials: 68.5% ethylene-vinyl acetate copolymer resin (EVA), 9% acid-resistant and aging-resistant masterbatch, 15% dripping masterbatch, 1.5% defogging masterbatch, and 6% thermal insulation masterbatch; the inner 1 layer is the acid-resistant dripping and defogging agent release layer, calculated by mass percentage, the inner 1 layer is composed of the following raw materials: 79% ethylene-vinyl acetate copolymer resin (EVA), 9% acid-resistant and aging-resistant masterbatch, 11% dripping masterbatch, and 1% defogging masterbatch.

[0132] The raw materials for the outer layer 1 are: metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 1.0 g / 10 min, brand 2010MA, manufactured by ExxonMobil; acid-resistant and aging-resistant masterbatch (self-made); and dust-proof masterbatch brand EFT997, manufactured by Tianjin Riken Co., Ltd.

[0133] The raw material composition and preparation process of the acid-resistant and aging-resistant masterbatch are exactly the same as those of the outer layer 1 in Example 1.

[0134] Among the raw materials of the outer two layers: low-density polyethylene (LDPE) with a melt index (MI) of 0.25 g / 10 min, brand 2420D, manufactured by Daqing Petrochemical; linear low-density polyethylene (LLDPE), with a melt index (MI) of 0.85 g / 10 min, brand 9085, manufactured by Tianjin Lianhua; metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 1.0 g / 10 min, brand 1018MA, manufactured by ExxonMobil; acid-resistant and aging-resistant masterbatch (self-made), and light-conversion masterbatch (self-made).

[0135] The raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch are exactly the same as those of the outer layer 1 in Example 1.

[0136] In terms of mass percentage, the light conversion masterbatch in the outer two layers is composed of the following raw materials: 45% low-density polyethylene (LDPE), 39.6% linear low-density polyethylene (LLDPE), 15% light conversion agent, and 0.4% antioxidant; among which: low-density polyethylene (LDPE) 2102TN00 is manufactured by Qilu Petrochemical; powdered linear low-density polyethylene (LLDPE) 7042 is manufactured by Qilu Petrochemical; the light conversion agent is purple-to-red VTR660 and purple-to-blue VTB440, compounded in a mass ratio of 2:3, manufactured by Hunan Xiweier Technology Co., Ltd., and the antioxidant B215 is manufactured by Tianjin Lianlong.

[0137] The preparation method of the light conversion masterbatch is exactly the same as that of the outer two layers in Example 1.

[0138] Among the raw materials of the outer three layers: low-density polyethylene (LDPE) with a melt index (MI) of 0.25 g / 10 min, brand 2420D manufactured by Daqing Petrochemical; metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 0.5 g / 10 min, brand 2705MC manufactured by ExxonMobil. The raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the outer three layers are exactly the same as those of the outer layer 1 in Example 1. The raw material composition and preparation method of the thermal insulation masterbatch in the outer three layers are exactly the same as those of the outer three layers in Example 1.

[0139] The raw materials of the middle layer include: ethylene-vinyl acetate copolymer resin (EVA), VA content 19%, melt index (MI) 0.65g / 10min, brand 00119, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the middle layer are exactly the same as those of the outer layer 1 in Example 1; the raw material composition and preparation method of the thermal insulation masterbatch in the middle layer are exactly the same as those of the outer 3 layers in Example 1. The raw material composition and preparation method of the drip masterbatch in the middle layer are exactly the same as those of the middle layer in Example 1.

[0140] The raw materials of the inner three layers are: ethylene-vinyl acetate copolymer resin (EVA), VA content 14%, melt index (MI) 0.25g / 10min, brand FL00014, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the inner three layers are exactly the same as those of the outer one layer in Example 1; the raw material composition and preparation method of the thermal insulation masterbatch in the inner three layers are exactly the same as those of the outer three layers in Example 1. The raw material composition and preparation method of the drip masterbatch in the inner three layers are exactly the same as those of the middle layer in Example 1.

[0141] The raw materials of the inner 2 layers: ethylene-vinyl acetate copolymer resin (EVA), VA content of 12%, melt index (MI) of 0.5g / 10min, brand FL00012, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the inner 2 layers are exactly the same as those of the outer 1 layer in Example 1; the raw material composition and preparation method of the thermal insulation masterbatch in the inner 2 layers are exactly the same as those of the outer 3 layers in Example 1. The raw material composition and preparation method of the drip masterbatch in the inner 2 layers are exactly the same as those of the middle layer in Example 1. The raw material composition and preparation method of the defogging masterbatch in the inner 2 layers are exactly the same as those of the inner 2 layers in Example 1.

[0142] The raw materials of the inner layer 1 are: ethylene-vinyl acetate copolymer resin (EVA), VA content 7.5%, melt index (MI) 0.5g / 10min, brand 00111, produced by ExxonMobil; the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the inner layer 1 are exactly the same as those of the outer layer 1 in Example 1. The raw material composition and preparation method of the drip masterbatch in the inner layer 1 are exactly the same as those of the middle layer in Example 1. The raw material composition and preparation method of the defogging masterbatch in the inner layer 1 are exactly the same as those of the inner 2 layers in Example 1.

[0143] The preparation method and process conditions of the internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film described in this Example 5 are exactly the same as those in Example 1.

[0144] The seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-lasting drip-and-fog-eliminating greenhouse film prepared in this embodiment 5 has a product specification of 12000 / 0.12mm; the designed service life is 2 years. The light transmittance is 90.8%, the haze is 15.6%, and the duration of the drip-and-fog-eliminating function is 24 months after the greenhouse buckle verification. The light-converting agent is a compound of purple-to-blue VTB440 and purple-to-red VTR660, so that the greenhouse film has the function of converting part of the ultraviolet light excitation spectrum 290-370nm into a blue light emission spectrum of 440nm and a red light emission spectrum of 660nm, enhancing the irradiation intensity of blue and red light, and improving the lighting environment in the greenhouse. It is suitable for covering tobacco and rice seedlings, and is also suitable for covering all green leafy vegetables, so that the stems are thick, the leaves are thick, and the yield is high quality. The addition of dust-proof masterbatch makes the greenhouse film bright as new after being exposed to wind and rain, and the light transmittance does not decrease significantly. The addition of high thermal insulation resin EVA and thermal insulation masterbatch acts as a drip agent reserve and slow-release carrier, and makes the transmittance of infrared radiation from the greenhouse to the outside at night low; the greenhouse film prepared in Example 5 has been demonstrated for field application in Hunan, Hubei and Fujian in October 2022, and the tobacco seedling effect has thick and wide leaves and thick rhizomes; the greenhouse film prepared in Example 5 was tested and demonstrated at the Hunan Bangbo Science and Technology Park base, and the yield of water spinach covered by the planting increased by 21.6%. The greenhouse film prepared in Example 5 was evaluated by experts and determined to be a special film for seedling cultivation and green leafy vegetables.

[0145] Comparative Example 1

[0146] The seven-layer co-extruded light-converting, high-insulation, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film of the internally added polyolefin described in this comparative example 1 is composed of an outer layer 1, an outer layer 2, an outer layer 3, a middle layer, an inner layer 3, an inner layer 2 and an inner layer 1; wherein the outer layer 1 is an aging-resistant layer, and in terms of mass percentage, the outer layer 1 is composed of the following raw materials: 90% of metallocene linear low-density polyethylene (mLLDPE) and 10% of acid-resistant and aging-resistant masterbatch; the outer layer 2 is a light-converting and aging-resistant layer, and in terms of mass percentage, the outer layer 2 is composed of the following raw materials: low-density polyethylene (LDPE) 21%, linear low-density polyethylene (LLDPE) 15%, metallocene linear low-density polyethylene (mLLDPE) 45%, acid-resistant and aging-resistant masterbatch 8%, light-conversion masterbatch 11%; the outer three layers are barrier, heat-insulating, acid-resistant and aging-resistant layers. In terms of mass percentage, the outer three layers are composed of the following raw materials: low-density polyethylene (LDPE) 15%, metallocene linear low-density polyethylene (mLLDPE) 63%, acid-resistant and aging-resistant masterbatch 10%, and heat-insulating masterbatch 12%; the middle layer is high The thermal insulation and acid-resistant dripping agent reserve layer is composed of the following raw materials in the middle layer by mass percentage: 62% ethylene-vinyl acetate copolymer resin (EVA), 8% acid-resistant and aging-resistant masterbatch, 20% dripping masterbatch, and 10% thermal insulation masterbatch; the inner three layers are high thermal insulation and acid-resistant dripping agent reserve layers, and the inner three layers are composed of the following raw materials in mass percentage: 65% ethylene-vinyl acetate copolymer resin (EVA), 9% acid-resistant and aging-resistant masterbatch, 17% dripping masterbatch, and 9% thermal insulation masterbatch; the inner two layers are high thermal insulation and acid-resistant The drip and defogging agent sustained-release layer, calculated by mass percentage, the inner 2 layers are composed of the following raw materials: 67.5% ethylene-vinyl acetate copolymer resin (EVA), 10% acid and aging resistant masterbatch, 15% drip masterbatch, 1.5% defogging masterbatch, and 6% thermal insulation masterbatch; the inner 1 layer is the acid and resistant drip and defogging agent release layer, calculated by mass percentage, the inner 1 layer is composed of the following raw materials: 78% ethylene-vinyl acetate copolymer resin (EVA), 9% acid and aging resistant masterbatch, 12% drip masterbatch, and 1% defogging masterbatch.

[0147] The raw materials for the outer layer 1 are: metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 1.0 g / 10 min, brand 2010MA, manufactured by ExxonMobil; acid-resistant and aging-resistant masterbatch (self-made).

[0148] The composition and preparation method of the acid-resistant and aging-resistant masterbatch in the outer layer raw material are exactly the same as those of the outer layer in Example 1.

[0149] Among the raw materials of the outer two layers: low-density polyethylene (LDPE) with a melt index (MI) of 0.25 g / 10 min, brand 2420D, manufactured by Daqing Petrochemical; linear low-density polyethylene (LLDPE), with a melt index (MI) of 0.85 g / 10 min, brand 9085, manufactured by Tianjin Union Carbide; metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 1.0 g / 10 min, brand 1018MA, manufactured by ExxonMobil; acid-resistant and aging-resistant masterbatch (self-made), and light-conversion masterbatch (self-made).

[0150] The raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch are exactly the same as those of the outer layer 1 in Example 1.

[0151] The raw material composition and preparation method of the light conversion masterbatch are exactly the same as those of the outer two layers in Example 1.

[0152] The raw material composition and raw material brand of the outer 3 layers, the middle layer, the inner 3 layers, the inner 2 layers and the inner 1 layer are exactly the same as those in Example 1.

[0153] The process parameters of the preparation process of this comparative example 1 are exactly the same as those of Example 1, and will not be described again. The specifications of the prepared product are 12000 / 0.12mm, the light transmittance is 89.7%, and the haze is 15.7%.

[0154] The difference between Comparative Example 1 and Example 1 is that no dust-proof masterbatch is added to the outer layer 1, and the greenhouse film does not have a dust-proof function. Dust is adsorbed on the surface of the greenhouse film, and it is not clean even when washed by rain and snow, and microbial plaque is produced, which directly affects the light transmittance and significantly reduces the light conversion efficiency. Other high thermal insulation, pesticide resistance, and drip and defogging properties are comparable.

[0155] The initial light transmittance of the greenhouse film prepared in this comparative example 1 is 89.7%, and the haze is 15.7%. In October 2022, the greenhouse films prepared in this comparative example 1 and Example 1 were subjected to a spliced ​​greenhouse control field application test at the Shandong Agricultural University Experimental Base in Lujiazhuang, Fangxia Town, Laiwu. The yield of sweet peppers planted in March 2023 was 5.75% lower than that of Example 1, and the picking period was delayed by 3 days; the yield of the second crop of kidney beans was 7.36% lower than that of Example 1.

[0156] Comparative Example 2

[0157] The seven-layer co-extruded dustproof, high-insulation, pesticide-resistant, long-acting drip-and-fog-eliminating shed film of the internally added polyolefin described in this comparative example 2 is composed of an outer layer 1, an outer layer 2, an outer layer 3, a middle layer, an inner layer 3, an inner layer 2 and an inner layer 1; wherein the outer layer 1 is a dustproof and aging-resistant layer, and the outer layer 1 is composed of the following raw materials by mass percentage: 82% of metallocene linear low-density polyethylene (mLLDPE), 9% of acid-resistant and aging-resistant masterbatch, and 9% of dustproof masterbatch; the outer layer 2 is an aging-resistant layer, and the outer layer 2 is composed of the following raw materials by mass percentage : Low-density polyethylene (LDPE) 23%, linear low-density polyethylene (LLDPE) 17%, metallocene linear low-density polyethylene (mLLDPE) 50%, acid-resistant and aging-resistant masterbatch 10%; the outer three layers are barrier, thermal insulation, acid-resistant and aging-resistant layers. In terms of mass percentage, the outer three layers are composed of the following raw materials: low-density polyethylene (LDPE) 20%, metallocene linear low-density polyethylene (mLLDPE) 60%, acid-resistant and aging-resistant masterbatch 9%, thermal insulation masterbatch 11%; the middle layer is high The thermal insulation and acid-resistant dripping agent reserve layer is composed of the following raw materials in the middle layer by mass percentage: 62% ethylene-vinyl acetate copolymer resin (EVA), 9% acid-resistant and aging-resistant masterbatch, 20% dripping masterbatch, and 9% thermal insulation masterbatch; the inner three layers are high thermal insulation and acid-resistant dripping agent reserve layers, and the inner three layers are composed of the following raw materials in mass percentage: 66% ethylene-vinyl acetate copolymer resin (EVA), 8% acid-resistant and aging-resistant masterbatch, 17% dripping masterbatch, and 9% thermal insulation masterbatch; the inner two layers are high thermal insulation and acid-resistant The drip and defogging agent sustained-release layer, calculated by mass percentage, the inner 2 layers are composed of the following raw materials: 68.5% ethylene-vinyl acetate copolymer resin (EVA), 9% acid and aging resistant masterbatch, 14% drip masterbatch, 1.5% defogging masterbatch, and 7% thermal insulation masterbatch; the inner 1 layer is the acid and resistant drip and defogging agent release layer, calculated by mass percentage, the inner 1 layer is composed of the following raw materials: 79% ethylene-vinyl acetate copolymer resin (EVA), 9% acid and aging resistant masterbatch, 11% drip masterbatch, and 1% defogging masterbatch.

[0158] The raw materials for the outer layer 1 are: metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 1.0 g / 10 min, brand 2010MA, manufactured by ExxonMobil; acid-resistant and aging-resistant masterbatch (self-made); and dust-proof masterbatch brand EFT997, manufactured by Tianjin Riken Co., Ltd.

[0159] The raw material composition and preparation process of the acid-resistant and aging-resistant masterbatch are exactly the same as those of the outer layer 1 in Example 2.

[0160] Among the raw materials for the outer two layers: low-density polyethylene (LDPE) with a melt index (MI) of 0.25 g / 10 min, brand 2420D, manufactured by Daqing Petrochemical; linear low-density polyethylene (LLDPE), with a melt index (MI) of 0.85 g / 10 min, brand 9085, manufactured by Tianjin Lianhua; metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 1.0 g / 10 min, brand 1018MA, manufactured by ExxonMobil; acid-resistant and aging-resistant masterbatch (self-made); the raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch are exactly the same as those of the outer layer 1 in Example 2.

[0161] The raw material composition and grades in the outer 3 layers, the middle layer, the inner 3 layers, the inner 2 layers and the inner 1 layer are exactly the same as those in Example 2.

[0162] The raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch are exactly the same as those of the outer layer 1 in Example 2.

[0163] The preparation method and process conditions of the internally added polyolefin seven-layer co-extruded dust-proof, high-insulation, pesticide-resistant, long-acting dripping and fog-eliminating shed film described in this comparative example 2 are exactly the same as those in Example 1. The prepared product specification is 12000 / 0.12mm; the light transmittance is 90.2%, the haze is 15.2%, and the designed service life is 2 years.

[0164] The difference between this comparative example 2 and example 2 is that no light conversion masterbatch is added, and it does not have the light conversion function, and the light intensity ratio in the shed is significantly reduced. This comparative example 2 and example 2 are made into a spliced ​​shed. In October 2022, the field application demonstration was carried out at the Shandong Agricultural University Experimental Base in Gaozhuang, Fangxia Town, Laiwu. The yield of strawberries (Sweet Treasure) planted was 20.7% lower than that of example 2, and the picking period was delayed by 5 days, which is a significant difference.

[0165] Comparative Example 3

[0166] The seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-acting dripping and fog-eliminating shed film of the internally added polyolefin described in this comparative example 3 is composed of an outer layer 1, an outer layer 2, an outer layer 3, a middle layer, an inner layer 3, an inner layer 2 and an inner layer 1; wherein the outer layer 1 is a dust-proof and aging-resistant layer, and the outer layer 1 is composed of the following raw materials by mass percentage: 83% of metallocene linear low-density polyethylene (mLLDPE), 9% of acid-resistant and aging-resistant masterbatch, and 8% of dust-proof masterbatch; the outer layer 2 is a light-converting and aging-resistant layer, and the outer layer 2 is composed of the following raw materials by mass percentage: Low-density polyethylene (LDPE) 25%, linear low-density polyethylene (LLDPE) 15%, metallocene linear low-density polyethylene (mLLDPE) 42%, acid-resistant and aging-resistant masterbatch 9%, light-converting masterbatch 9%; the outer three layers are acid-resistant and aging-resistant layers. In terms of mass percentage, the outer three layers are composed of the following raw materials: low-density polyethylene (LDPE) 22%, linear low-density polyethylene (LLDPE) 30%, metallocene linear low-density polyethylene (mLLDPE) 40%, acid-resistant and aging-resistant masterbatch 8%; the middle layer is a high thermal insulation and acid-resistant dripping agent reserve layer, which is composed of the following raw materials by mass percentage: 60% ethylene-vinyl acetate copolymer resin (EVA), 10% acid-resistant and aging-resistant masterbatch, 20% dripping masterbatch, and 10% thermal insulation masterbatch; the inner 3 layers are high thermal insulation and acid-resistant dripping agent reserve layers, which are composed of the following raw materials by mass percentage: 63% ethylene-vinyl acetate copolymer resin (EVA), 9% acid-resistant and aging-resistant masterbatch, 18% dripping masterbatch, and 10% thermal insulation masterbatch; the inner 2 layers are The high thermal insulation anti-acid dripping and defogging agent sustained-release layer, calculated by mass percentage, the inner 2 layers are composed of the following raw materials: 69.5% ethylene-vinyl acetate copolymer resin (EVA), 8% anti-acid and aging-resistant masterbatch, 15% dripping masterbatch, 1.5% defogging masterbatch, and 6% thermal insulation masterbatch; the inner 1 layer is the anti-acid dripping and defogging agent release layer, calculated by mass percentage, the inner 1 layer is composed of the following raw materials: 80% ethylene-vinyl acetate copolymer resin (EVA), 8% anti-acid and aging-resistant masterbatch, 11% dripping masterbatch, and 1% defogging masterbatch.

[0167] The raw material composition and brand of the outer layer 1 and the outer layer 2 are exactly the same as those of the outer layer 1 and the outer layer 2 of Example 3. The raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch are exactly the same as those of the outer layer 1 of Example 3. The raw material composition and preparation method of the light-converting masterbatch are exactly the same as those of the outer layer 2 of Example 3.

[0168] Among the raw materials of the outer three layers: low-density polyethylene (LDPE) with a melt index (MI) of 0.25 g / 10 min, grade 2420D, manufactured by Daqing Petrochemical; linear low-density polyethylene (LLDPE), with a melt index (MI) of 0.85 g / 10 min, grade 9085, produced by Tianjin Lianhua; metallocene linear low-density polyethylene (m-LLDPE), with a melt index (MI) of 1.0 g / 10 min, grade 1018 MA, manufactured by ExxonMobil. The raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch in the outer three layers are exactly the same as those of the outer one layer in Example 3.

[0169] The outer three layers of this comparative example 3 are not designed as a barrier layer for guiding the dripping agent to precipitate from the inner layer, that is, no high-density metallocene resin is used and no hydrotalcite insulation masterbatch is added, so the dripping agent cannot be blocked from migrating to the outer layer and precipitating.

[0170] The raw material composition and brand in the middle layer, inner 3 layers, inner 2 layers and inner 1 layer are exactly the same as those in the middle layer, inner 3 layers, inner 2 layers and inner 1 layer of Example 3.

[0171] The seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-lasting dripping and fog-eliminating greenhouse film prepared in this comparative example 3 has a product specification of 12000 / 0.12mm and a designed service life of 2 years. The light transmittance is 90.1% and the haze is 15.9%. After the greenhouse buckle verification, the dripping and fog-eliminating function lasts for 12 months.

[0172] The difference between the greenhouse film prepared in this comparative example 3 and the greenhouse film in example 3 is: the outer three layers of this comparative example 3 do not have a design scheme for guiding the drip agent to precipitate out from the inner layer, that is, the high-density metallocene resin is not used and the hydrotalcite thermal insulation masterbatch is not added, which fails to play a role in blocking the migration of the drip agent to the outer layer. The bidirectional migration of the drip agent causes waste and shortens the effectiveness of the drip function. The drip defogging function of the greenhouse film in this comparative example 3 will fail in October 2023.

[0173] The greenhouse film prepared in this comparative example 3 was tested with the greenhouse film of Example 3 for splicing greenhouses. In October 2022, a field application demonstration was carried out at the Shandong Agricultural University Experimental Base in Gaozhuang, Fangxia Town, Laiwu. The tomatoes (Pioneer No. 4) planted in the comparative example 3 had a 0.5-1.0°C lower nighttime temperature in the greenhouse than that in Example 3, and the harvesting was delayed by 3 days.

[0174] Comparative Example 4

[0175] The seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-acting dripping and fog-eliminating shed film of the internally added polyolefin described in this comparative example 4 is composed of an outer layer 1, an outer layer 2, an outer layer 3, a middle layer, an inner layer 3, an inner layer 2 and an inner layer 1; wherein the outer layer 1 is a dust-proof and aging-resistant layer, and the outer layer 1 is composed of the following raw materials in terms of mass percentage: 84% of metallocene linear low-density polyethylene (mLLDPE), 8% of acid-resistant and aging-resistant masterbatch, and 8% of dust-proof masterbatch; the outer 2 layers are light-converting and aging-resistant layers, and the outer 3 layers are middle layers, inner 3 layers, inner 2 layers and inner 1 layer ... layer 2 is a light-converting and aging-resistant layer, and the outer layer 1 is middle layers, inner 3 layers, inner 2 layers and inner 1 layer; wherein the outer layer 1 is a dust-proof and aging-resistant layer, and the outer layer 1 is middle layers The second layer is composed of the following raw materials: low-density polyethylene (LDPE) 28%, linear low-density polyethylene (LLDPE) 16%, metallocene linear low-density polyethylene (mLLDPE) 35%, acid-resistant and aging-resistant masterbatch 11%, and light-converting masterbatch 10%; the outer three layers are barrier, heat-insulating, acid-resistant and aging-resistant layers. In terms of mass percentage, the outer three layers are composed of the following raw materials: low-density polyethylene (LDPE) 18%, metallocene linear low-density polyethylene (mLLDPE) 62%, anti- The middle layer is an acid-resistant dripping agent reserve layer, which is composed of the following raw materials by mass percentage: ethylene-vinyl acetate copolymer resin (EVA) 70%, acid-resistant and aging-resistant masterbatch 9%, and dripping masterbatch 21%; the inner 3 layers are acid-resistant dripping agent reserve layers, which are composed of the following raw materials by mass percentage: ethylene-vinyl acetate copolymer resin (EVA) 76%, acid-resistant and aging-resistant masterbatch 8%, and dripping masterbatch 16%; the inner 2 layers are acid-resistant dripping agent reserve layers, which are composed of the following raw materials by mass percentage: ethylene-vinyl acetate copolymer resin (EVA) 76%, acid-resistant and aging-resistant masterbatch 8%, and dripping masterbatch 16%; the inner 2 layers are acid-resistant dripping agent reserve layers, which are composed of the following raw materials by mass percentage: It is an anti-acid drip and defogging agent sustained-release layer. Calculated by mass percentage, the inner 2 layers are composed of the following raw materials: 75.5% ethylene-vinyl acetate copolymer resin (EVA), 9% anti-acid and aging-resistant masterbatch, 14% drip masterbatch, and 1.5% defogging masterbatch; the inner 1 layer is an anti-acid drip and defogging agent release layer. Calculated by mass percentage, the inner 1 layer is composed of the following raw materials: 79% ethylene-vinyl acetate copolymer resin (EVA), 9% anti-acid and aging-resistant masterbatch, 11% drip masterbatch, and 1% defogging masterbatch.

[0176] The raw material composition and brand of outer layer 1, outer layer 2 and outer layer 3 are exactly the same as those of outer layer 1, outer layer 2 and outer layer 3 in Example 4; the raw material composition and preparation process of the acid-resistant and aging-resistant masterbatch are exactly the same as those of outer layer 1 in Example 4; the raw material composition and preparation method of the light-converting masterbatch described in outer layer 2 are exactly the same as those of outer layer 2 in Example 4; the raw material composition and preparation method of the thermal insulation masterbatch in outer layer 3 are exactly the same as those of outer layer 3 in Example 4.

[0177] The raw material brands of the middle layer, inner 3 layers, inner 2 layers and inner 1 layer are exactly the same as those of the middle layer, inner 3 layers, inner 2 layers and inner 1 layer in Example 4; the difference is that the hydrotalcite insulation masterbatch in the middle layer, inner 3 layers and inner 2 layers of this comparative example 4 is replaced by EVA.

[0178] The raw material composition and preparation method of the acid-resistant and aging-resistant masterbatch are exactly the same as those of the outer layer 1 of Example 4; the raw material composition and preparation method of the drip masterbatch are exactly the same as those of the middle layer of Example 1. The raw material composition and preparation method of the defogging masterbatch are exactly the same as those of the inner 2 layers of Example 4.

[0179] The preparation method and process conditions of the internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film described in this comparative example 4 are exactly the same as those in Example 4.

[0180] The internally added polyolefin seven-layer co-extruded light-converting dust-proof, high-insulation, pesticide-resistant, long-lasting drip and fog-eliminating shed film prepared in this comparative example 4 has a product specification of 12000 / 0.12mm; the designed service life is 2 years. The light transmittance is 90.4%, the haze is 15.6%, and the drip and fog-eliminating function lasts for 17 months after the shed buckle verification. Compared with Example 4, this comparative example 4 does not add hydrotalcite insulation masterbatch to the middle layer, the inner 3 layers, and the inner 2 layers, which reduces the sustained release of the drip agent and is not conducive to prolonging the drip lasting performance. This comparative example 4 and Example 4 were used as a spliced ​​shed for field application demonstration at the Shandong Agricultural University Experimental Base in Gaozhuang, Fangxia Town, Laiwu in October 2022. The night temperature in the shed was 0.7-1.5℃ lower than that in Example 4, and the planted blueberries were picked 4 days later; the drip performance of this comparative example 4 failed in April 2024, and the drip lasted for 17 months.

[0181] Comparative Example 5

[0182] The seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film of the internally added polyolefin described in this comparative example 5 is composed of an outer layer 1, an outer layer 2, an outer layer 3, a middle layer, an inner layer 3, an inner layer 2 and an inner layer 1; wherein the outer layer 1 is a dust-proof and aging-resistant layer, and in terms of mass percentage, the outer layer 1 is composed of the following raw materials: 83% of metallocene linear low-density polyethylene (mLLDPE), 8% of aging-resistant masterbatch, and 9% of dust-proof masterbatch; the outer layer 2 is a light-converting and aging-resistant layer, and in terms of mass percentage, the outer layer 2 is composed of The following raw materials are composed of: low-density polyethylene (LDPE) 24%, linear low-density polyethylene (LLDPE) 20%, metallocene linear low-density polyethylene (mLLDPE) 35%, aging-resistant masterbatch 10%, and light-converting masterbatch 11%; the outer three layers are barrier, heat-insulating, and aging-resistant layers. In terms of mass percentage, the outer three layers are composed of the following raw materials: low-density polyethylene (LDPE) 16%, metallocene linear low-density polyethylene (mLLDPE) 63%, aging-resistant masterbatch 9%, and heat-insulating masterbatch 10%. The middle layer is a high thermal insulation dripping agent reserve layer, which is composed of the following raw materials by mass percentage: ethylene-vinyl acetate copolymer resin (EVA) 62%, aging-resistant masterbatch 8%, dripping masterbatch 21%, and thermal insulation masterbatch 9%; the inner three layers are high thermal insulation dripping agent reserve layers, which are composed of the following raw materials by mass percentage: ethylene-vinyl acetate copolymer resin (EVA) 65%, aging-resistant masterbatch 9%, dripping masterbatch 17%, and thermal insulation masterbatch 9%; the inner two layers are high The thermal insulation drip and defogging agent sustained-release layer, calculated by mass percentage, the inner 2 layers are composed of the following raw materials: ethylene-vinyl acetate copolymer resin (EVA) 68.5%, aging-resistant masterbatch 9%, drip masterbatch 15%, defogging masterbatch 1.5%, thermal insulation masterbatch 6%; the inner 1 layer is the drip and defogging agent release layer, calculated by mass percentage, the inner 1 layer is composed of the following raw materials: ethylene-vinyl acetate copolymer resin (EVA) 79%, aging-resistant masterbatch 9%, drip masterbatch 11%, defogging masterbatch 1.0%.

[0183] The raw material composition and brand of the outer layer 1, outer layer 2, and outer layer 3 are exactly the same as those in Example 5. The raw material composition and preparation process of the acid-resistant and aging-resistant masterbatch in each layer are exactly the same as those of the outer layer 1 in Example 5; the difference between this comparative example 5 and Example 5 is that the brand of the light stabilizer in the acid-resistant and aging-resistant masterbatch is HALS944, manufactured by BASF. The preparation method of the light-converting masterbatch is exactly the same as that of the outer layer 2 in Example 5. The raw material composition and preparation method of the thermal insulation masterbatch are exactly the same as those of the outer layer 3 in Example 5.

[0184] The raw material composition of the middle layer, inner 3 layers, inner 2 layers and inner 1 layer is exactly the same as that of Example 5, except that the EVA brand in the middle layer, inner 3 layers, inner 2 layers and inner 1 layer of this comparative example 5 is FL00012, with a VA content of 12%, produced by Exxon.

[0185] The preparation method and process conditions of the internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film described in this comparative example 5 are exactly the same as those in Example 5.

[0186] The seven-layer co-extruded light-converting, dust-proof, high-insulation, pesticide-resistant, long-lasting dripping and fog-eliminating greenhouse film prepared in this comparative example 5 has a product specification of 12000 / 0.12mm and a designed service life of 2 years. The light transmittance is 89.9%, the haze is 16.6%, and the duration of the dripping and fog-eliminating function is 15 months after the greenhouse buckle verification. This comparative example 5 is designed to resist S≤600PPM; Cl≤100PPM, and is only suitable for seedling cultivation or organic vegetable planting with less use of pesticides.

[0187] Compared with Example 5, the EVA grades in the middle layer, inner 3 layers, inner 2 layers and inner 1 layer of this comparative example 5 are all FL00012, and the VA content is 12%. The storage and sustained release of the drip agent in the middle layer, inner 3 layers and inner 1 layer are not as good as those in Example 5. The precipitation of the drip agent is too fast, which is not conducive to prolonging the drip lasting performance. This comparative example 5 and Example 5 were used as a splicing shed for field application demonstration at the Lujiazhuang Experimental Base of Shandong Agricultural University in Laiwu in October 2022. The drip performance of this comparative example 5 failed in January 2024, and the drip lasting period was 15 months.

[0188] According to the technical requirements of the national standard GB / T20202-2019, the mechanical properties, optical properties, infrared transmittance and dripping performance test results are shown in Table 2. The product specification is 12m*0.10mm.

[0189] Table 2 Test results of various performances of samples

[0190]

[0191] The test results reflected in Table 2 show that the mechanical properties, optical properties, and infrared transmittance data of Examples 1-5 and Comparative Examples 1-5 are all better than the national standard index requirements, and can meet the most basic requirements for greenhouse covering purposes. Comparative Example 3, which does not set a barrier layer, has an infrared transmittance that is 69.39% higher than that of Comparative Example 3; the drip failure time is reduced by 48%. Comparative Example 4 does not use hydrotalcite insulation masterbatch, and the infrared transmittance is increased by 119.2% compared with that of Comparative Example 4; the drip failure time is reduced by 30.2%. Comparative Example 5 does not use EVA resin with differentiated VA content to establish a system for storing and slowly releasing dripping agents, and the drip failure time is reduced by 38.5% compared with Comparative Example 5.

[0192] Table 3 Test results of indoor and outdoor light intensity ratio in the light conversion shed

[0193]

[0194] The test data of the indoor and outdoor light intensity ratio of the light conversion effect listed in Table 3 are the test results collected on the field film of the greenhouse using a handheld portable fluorescence spectrometer and illuminometer at the experimental base of the Agricultural University in Fangxia Town, Laiwu, and the demonstration base of Hunan Bangbo Science and Technology Park. The test data in Table 4 show that the indoor and outdoor light intensity ratio of Examples 1-5 decreases slightly with the extension of the greenhouse time, and the indoor and outdoor light intensity ratio remains above 88% after 20 months of greenhouse covering. The light conversion effect is significantly better than the 8-month record in the prior art, which remains above 88%. High light intensity ratio plays a key role in enhancing the photosynthetic efficiency of crops, promoting crop growth, early maturity and increasing yield, and improving quality. The indoor and outdoor light intensity ratio of the greenhouse tested after 600 days of covering decreased by 14.06% for Comparative Example 1 compared with Example 1, decreased by 14.56% for Comparative Example 2 compared with Example 2, decreased by 3.62% for Comparative Example 3 compared with Example 3, decreased by 4.51% for Comparative Example 4 compared with Example 4, and decreased by 4.07% for Comparative Example 5 compared with Example 5. It can be seen that not adding dust-proof agent or light conversion agent has a greater impact on the indoor and outdoor light intensity ratio of the greenhouse.

[0195] Table 4 Dustproof test results

[0196]

[0197]

[0198] In Table 4, light transmittance ≥ 85% is excellent, 85> light transmittance ≥ 80% is good, 80> light transmittance ≥ 75% is fair, and light transmittance < 75% is poor. Due to the effect of dust-proof masterbatch, the friction coefficient (0.1±0.01) of the greenhouse film surface is greatly reduced, dust and microorganisms are not easy to adhere to the film surface, and it is bright as new after being blown by wind and rain, and the influence on the attenuation rate of light transmittance is significantly reduced. The attenuation rate of this embodiment in 1-5 years is less than 1.05%, among which: the annual attenuation rate of light transmittance of embodiment 1, embodiment 3, and embodiment 4 is 1.0%, and the annual attenuation rate of light transmittance of embodiment 2 and embodiment 5 is 1.05%, which is 30% higher than the annual attenuation rate of 1.5% of the existing advanced technology level in the agricultural film industry. Low annual attenuation rate of light transmittance is a necessary condition for the long-term use of greenhouse film. Compared with Examples 1-5, the average annual attenuation rate of light transmittance of Example 1 is 6.02%, the average annual attenuation rate of light transmittance of Example 2 is 1.72%, the average annual attenuation rate of light transmittance of Example 3 is 3.33%, the average annual attenuation rate of light transmittance of Example 4 is 1.49%, and the average annual attenuation rate of light transmittance of Example 5 is 1.84%. The higher average annual attenuation rate of light transmittance is due to the fact that no dust-proof agent is added or no barrier layer is provided, which allows the drip agent to precipitate in both directions.

[0199] The acid and weather resistance of the greenhouse films prepared in Examples 1-5 were tested. The experimental equipment used a xenon lamp climate aging box and the test was carried out according to the plastic laboratory light source exposure test method GB / T16422.2-2014; the irradiation method was method A, and the irradiance was narrow band (340nm) 0.51W / (m 2 ·nm), black mark temperature 65℃ for aging test, spray for 18min, stop for 102min, take out the sample once a week during the test period and soak it in 0.1mol / L sulfurous acid solution for 24hr, clamp the test samples on the sample rack for irradiation spray cycle, one-year life greenhouse film test according to 1000 hours, two-year sample test 2200 hours, complete the test cycle. The test items are tensile strength retention rate and fracture nominal strain retention rate, and the technical requirements specified in the standard are: tensile strength retention rate ≥ 60%, fracture nominal strain retention rate ≥ 60%.

[0200] Table 5 Tensile strength test results

[0201]

[0202] Table 6 Tensile strength retention test results

[0203] Experiment time / h Measurement results Example 1 Example 2 Example 3 Example 4 Example 5 0 Tensile strength retention rate / % 100 100 100 100 100 2200 Tensile strength retention rate / % 65.49 63.92 65.88 64.76 65.96

[0204] Table 7 Elongation at break test results

[0205]

[0206] Table 8 Test results of elongation at break retention rate

[0207]

[0208] The above experimental data verify that the aging resistance of the greenhouse film samples prepared by the present invention is reliable and fully meets the technical requirements specified in GB / T20202-2019.

Claims

1. An internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-heat-insulating, pesticide-resistant, long-lasting dripping and fog-eliminating greenhouse film, characterized by: It consists of an outer layer 1, an outer layer 2, an outer layer 3, a middle layer, an inner layer 3, an inner layer 2 and an inner layer 1; wherein the outer layer 1 is a dustproof and aging-resistant layer, and is composed of the following raw materials by mass percentage: 80%-88% of metallocene linear low-density polyethylene, 5%-10% of acid-resistant and aging-resistant masterbatch, and 7%-10% of dustproof masterbatch; the outer layer 2 is a light-converting and aging-resistant layer, and is composed of the following raw materials by mass percentage: 20%-30% of low-density polyethylene, 15%-25% of linear low-density polyethylene, and metallocene Linear low-density polyethylene 35%-45%, light conversion masterbatch 8%-12%, acid-resistant and aging-resistant masterbatch 5%-10%; the outer three layers are barrier, heat-insulating, acid-resistant and aging-resistant layers. In terms of mass percentage, the outer three layers are composed of the following raw materials: low-density polyethylene 15%-25%, metallocene linear low-density polyethylene 55%-65%, acid-resistant and aging-resistant masterbatch 5%-10%, insulation masterbatch 10%-15%; the middle layer is a high-insulation and acid-resistant dripping agent reserve layer. In terms of mass percentage, the middle layer is composed of the following raw materials: ethylene -vinyl acetate copolymer resin 57%-68%, acid-resistant and aging-resistant masterbatch 5%-10%, drip masterbatch 15%-25%, thermal insulation masterbatch 8%-12%; the inner 3 layers are high thermal insulation and acid-resistant drip agent reserve layers. In terms of mass percentage, the inner 3 layers are composed of the following raw materials: ethylene-vinyl acetate copolymer resin 60%-72%, acid-resistant and aging-resistant masterbatch 5%-10%, drip masterbatch 15%-18%, thermal insulation masterbatch 8%-12%; the inner 2 layers are high thermal insulation and acid-resistant drip defogging agent sustained-release layers. In terms of mass percentage, the inner 2 layers are high thermal insulation and acid-resistant drip defogging agent sustained-release layers. In terms of percentage, the inner two layers are composed of the following raw materials: 67%-72% ethylene-vinyl acetate copolymer resin, 5%-10% acid and aging resistant masterbatch, 12%-15% drip masterbatch, 1%-3% defogging masterbatch, and 5%-8% thermal insulation masterbatch; the inner 1 layer is the acid and resistant drip defogging agent release layer, and in terms of mass percentage, the inner 1 layer is composed of the following raw materials: 77%-84% ethylene-vinyl acetate copolymer resin, 5%-10% acid and aging resistant masterbatch, 8%-12% drip masterbatch, and 1%-3% defogging masterbatch.

2. The internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-heat-insulating, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film according to claim 1 is characterized by: The specific parameters of the raw materials used in the outer 3 layers, outer 2 layers, and outer 1 layer are as follows: the density of low-density polyethylene is 0.920-0.923 g / cm 3 , melt index (MI) is 0.2-0.75g / 10min; The density of linear low-density polyethylene is 0.918-0.922 g / cm 3 , melt index is 0.8-1.0g / 10min; The density of metallocene linear low-density polyethylene is 0.918-0.927 g / cm 3 , melt index is 0.5-1.0g / 10min; The dust-proof masterbatch is a grade EFT997 or a grade BE-10F maleic anhydride grafted dust-proof masterbatch produced by Tianjin Riken Co., Ltd., and the manufacturer is Jilin Baien Plastic Technology Co., Ltd.

3. The internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-heat-insulating, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film according to claim 1 is characterized by: In terms of mass percentage, the acid-resistant and aging-resistant masterbatch is composed of the following raw materials: 45%-53% low-density polyethylene, 30%-40% linear low-density polyethylene, 12%-15% light stabilizer, and 2%-3% antioxidant; Wherein: the melt index of low-density polyethylene is 2.0g / 10min; the melt index of linear low-density polyethylene is 2.0g / 10min; the light stabilizer is a hindered amine acid-resistant light stabilizer, and the hindered amine acid-resistant light stabilizer is at least one of 2011AR, XT-100 or T-69, the manufacturer of 2011AR and XT-100 is BASF, and the manufacturer of T-69 is Beijing Tiangang Company; the antioxidant is a hindered phenol and phosphite composite type, and the antioxidant is any one of B215 or B225; the manufacturer of B215 or B225 is Tianjin Lianlong Company; The preparation method of the acid-resistant and aging-resistant masterbatch is as follows: low-density polyethylene, linear low-density polyethylene, light stabilizer and antioxidant are added to an internal mixer in proportion for kneading and plasticization, and then fed to a single-screw extruder granulator through an open mixer, hot pelletized, and air-cooled and dried to obtain the acid-resistant and aging-resistant masterbatch; Wherein: the temperature of the internal mixer is 125-140°C, the plasticizing time is 15-20 minutes, and the temperature of the single-screw extruder granulator is 140-170°C.

4. The internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-heat-insulating, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film according to claim 1 is characterized by: The thermal insulation masterbatch is composed of the following raw materials in terms of mass percentage: 18%-25% low-density polyethylene, 15%-20% linear low-density polyethylene, 55%-65% hydrotalcite thermal insulation agent, 1.0%-2.0% coupling agent, 0.5%-1.5% lubricant, and 0.5%-1.5% dispersant; Wherein: the melt index of low-density polyethylene is 2.0g / 10min; the melt index of linear low-density polyethylene is 2.0g / 10min; the brand of hydrotalcite heat preservation agent is HTP, manufactured by Sakai Chemical Co., Ltd. of Japan, or any one of the brands HT3 produced by Dandong Kyowa Co., Ltd.; the coupling agent is any one of titanate or aluminate; the lubricant is two or any one of zinc stearate or calcium stearate; the dispersant is polyethylene wax; The preparation method of the thermal insulation masterbatch is as follows: low-density polyethylene, linear low-density polyethylene, hydrotalcite thermal insulation agent, coupling agent, lubricant and dispersant are added to an internal mixer in proportion for kneading and plasticization, and then fed to a single-screw extruder granulator through an open mixer, and then hot pelletized and air-cooled to obtain the thermal insulation masterbatch; Wherein: the temperature of the internal mixer is 125-140°C, the plasticizing time is 15-20 minutes, and the temperature of the single-screw extruder granulator is 140-170°C.

5. The internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-heat-insulating, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film according to claim 1 is characterized by: In terms of mass percentage, the light conversion masterbatch is composed of the following raw materials: 36.6%-49.8% low-density polyethylene, 38%-45% linear low-density polyethylene, 12%-18% light conversion agent, and 0.2%-0.4% antioxidant; Among them: the melt index of low-density polyethylene is 2.0g / 10min; the melt index of linear low-density polyethylene is 2.0g / 10min; the light conversion agent is an inorganic rare earth light conversion agent, and the inorganic rare earth light conversion agent is any one or more of green-to-red GTR-650Ⅱ, green-to-red GTR-650Ⅲ, purple-to-blue VTB-440 or purple-to-red VTR660; the antioxidant is a composite of hindered phenols and phosphites, and the antioxidant is any one of B215 or B225; the manufacturer of B215 or B225 is Tianjin Lianlong Company; The preparation method of the light conversion masterbatch is as follows: low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), a light conversion agent and an antioxidant are added to an internal mixer in proportion for kneading and plasticization, and then fed to a single-screw extruder granulator through an open mixer, and hot pelletized and air-cooled to obtain the light conversion masterbatch; Wherein: the temperature of the internal mixer is 125-140°C, the plasticizing time is 15-20 minutes, and the temperature of the single-screw extruder granulator is 140-170°C.

6. The internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-heat-insulating, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film according to claim 1 is characterized by: The melt index of the ethylene-vinyl acetate copolymer resin in the raw materials of the middle layer, the inner three layers, the inner two layers, and the inner one layer is 0.25-1.0g / 10min, wherein the VA content of the ethylene-vinyl acetate copolymer resin in the middle layer is 19%, the VA content of the ethylene-vinyl acetate copolymer resin in the inner three layers is 14%, the VA content of the ethylene-vinyl acetate copolymer resin in the inner two layers is 12%, and the VA content of the ethylene-vinyl acetate copolymer resin in the outer one layer is 7.5%.

7. The internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-heat-insulating, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film according to claim 1 is characterized by: In terms of mass percentage, the drip masterbatch in the raw materials of the middle layer, the inner three layers, the inner two layers, and the inner one layer is composed of the following raw materials: 37%-42% of ethylene-vinyl acetate resin, 30.6%-36.4% of linear low-density polyethylene, 18%-22% of drip agent, 0.4%-0.6% of antioxidant, and 5%-8% of ultrafine silicon dioxide; Wherein: the melt index of the ethylene-vinyl acetate resin in the drip masterbatch is 2.0 g / 10 min; the melt index of the linear low-density polyethylene is 2.0 g / 10 min; the drip agent is any one of KF650 or LD777; the antioxidant is any one of B215 or B225, and the manufacturer of B215 or B225 is Tianjin Lianlong Company; The preparation method of the drip masterbatch is as follows: ethylene-vinyl acetate resin, linear low-density polyethylene, drip agent, antioxidant and ultrafine silica are added to a high-speed mixer according to a proportion and kneaded, and then the kneaded material is fed into a twin-screw extruder granulator, and the drip masterbatch is obtained after being drawn, water-cooled, pelletized, dried and cooled; Wherein: the temperature of the high-speed mixer is 75-85°C, the kneading time is 12-15 minutes, and the temperature of the twin-screw extruder granulator is 150-175°C.

8. The internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-heat-insulating, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film according to claim 1 is characterized by: In terms of mass percentage, the defogging masterbatch in the raw materials of the inner 2 layers and the inner 1 layer is composed of the following raw materials: 45%-52% of ethylene-vinyl acetate resin, 35.9%-43.7% of linear low-density polyethylene, 8%-12% of defogging agent, and 0.1%-0.3% of antioxidant; Wherein: the melt index of the ethylene-vinyl acetate resin in the defogging masterbatch is 2.0 g / 10 min, and the VA content is 14%; the melt index of the linear low-density polyethylene is 2.0 g / 10 min; the defogging agent is any one of KF38 or TS403 fluorosurfactants, KF38 is produced by Tianjin Riken Kaisha, and TS403 is produced by Dalian Jinlong Chemical; the antioxidant is any one of B215 or B225; the manufacturers of B215 or B225 are Tianjin Lianlong Company; The preparation method of the defogging masterbatch is as follows: ethylene-vinyl acetate resin, linear low-density polyethylene, defogging agent and antioxidant are added into a high-speed mixer according to a proportion and kneaded, and then the kneaded material is fed into a twin-screw extruder granulator, and then subjected to strip drawing, water cooling, pelletizing, and entering a drying device, and then cooled to obtain the defogging masterbatch; Wherein: the temperature of the high-speed mixer is 75-85°C, the kneading time is 12-15 minutes, and the temperature of the twin-screw extruder granulator is 150-175°C.

9. A method for preparing the seven-layer co-extruded light-converting, dust-proof, high-heat-insulating, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film according to claim 1, characterized in that: The component materials of outer layer 1, outer layer 2, outer layer 3, middle layer, inner layer 3, inner layer 2 and inner layer 1 are mixed and stirred evenly respectively, added into a seven-layer co-extrusion extruder, and subjected to melt plasticization blow molding, cooling and shaping, pulling, seam splitting, edge welding, coding and marking, and winding to obtain an internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high heat preservation, pesticide-resistant, and long-acting dripping and fog-eliminating shed film.

10. The method for preparing the internally added polyolefin seven-layer co-extruded light-converting, dust-proof, high-heat-insulating, pesticide-resistant, long-acting dripping and fog-eliminating greenhouse film according to claim 9, characterized in that: In the seven-layer co-extrusion unit, the extruder temperatures of the outer layer 1, outer layer 2, outer layer 3, middle layer, inner layer 3, inner layer 2 and inner layer 1 are all 150-200°C, the die head temperature is 190-210°C, and the blow-up ratio is 1.5-2.5.

Citation Information

Patent Citations

  • Internal addition type long-acting dripping fog dispersal film

    CN110712410A

  • Coating type polyethylene pesticide-resistant dustproof high-heat-preservation long-acting dripping fog dissipation greenhouse film and preparation method thereof

    CN118633460A

Cited By

  • Seven-layer co-extrusion pesticide-resistant high-barrier agricultural film and production process thereof

    CN120003138A